Polarizing film laminate, optical display panel using the polarizing film laminate, polarizing film laminate with transparent adhesive layer, and polarizing film assembly
By adjusting the iodine concentration and moisture content of the polarizing film and adding a light absorbing layer to the polarizing film, the problems of 'polyethyleneization', 'decolorization' and 'heating red change' of the optical display panel in high temperature and high humidity environments are solved. A stable transmittance and reliability are achieved.
Patent Information
- Application Number
- CN202080060899.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-08-24
- Filing Date
- 2020-08-28
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2040-08-28
AI Technical Summary
The polarizing film laminates of existing optical display panels are prone to 'polyalkylation', 'decolorization' and 'heating red change' in high temperature or high humidity environments, resulting in a decrease in transmittance and a decrease in reliability. The prior art has not been fully integrated. Solve these problems.
By adjusting the iodine concentration of the polarizing film and the water content of the polarizing film laminate, and adding a light absorbing layer with light absorption ability to suppress the influence of ultraviolet, visible light and infrared rays in sunlight on the polarizing film. Specific implementation methods The polarizing film formed by using polyvinyl alcohol resin within a specific range of the iodine concentration and moisture content of the polarizing film, and is combined with a transparent adhesive layer and a cover plate to form a laminate having light absorption capacity.
It effectively solves the problems of 'polyalkylation', 'decolorization' and 'heating red change', ensuring the stability and transmittance of the optical display panel in high temperature and high humidity environments, and extending its service life.
Smart Images

Figure CN114303080B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a polarizing film laminate, an optical display panel using the polarizing film laminate, a polarizing film laminate with a transparent adhesive layer, and a polarizing film assembly. Background Art
[0002] In recent years, optical display panels such as liquid crystal panels and organic EL panels have been used in electronic devices such as smartphones and personal computers, and electrical products such as IoT home appliances. In addition, various possibilities have been found for their use in powered vehicles such as automobiles, trains, and airplanes. For example, it is conceivable to mount optical display panels on the windshield, dashboard, exterior, and other various parts of the vehicle body to provide various information to the driver and to transmit various information to the outside.
[0003] With such a situation, the durability in harsh environments such as in power-driven vehicles is required to be further improved. Due to the use environment such as high temperature or high humidity, or due to the irradiation of sunlight, the performance of the optical display panel, especially the polarizing film laminate (polarizer) used in the optical display panel, and the polarizing film (polarizer) used in the polarizing film laminate may be degraded, and in the worst case, it may even become unusable.
[0004] Patent Document 1 discloses an example of a polarizer having improved durability in a high temperature or high humidity environment, a polarizing plate using the polarizer, and a liquid crystal display device using the polarizing plate. As durability, red leakage (depolarization of long wavelength light) under crossed Nicols that occurs when placed under high temperature conditions is considered a problem, and in order to solve this problem, a scheme is proposed in which zinc is contained and the relationship between the zinc content and the iodine content is adjusted to a given range.
[0005] Similarly, Patent Document 2 relates to a polarizing plate for an in-vehicle image display device having improved durability in a high temperature or high humidity environment, wherein attention is paid to the moisture content of the polarizing plate and the saturated water absorption of the protective film. In-vehicle polarizing plates are required to have high temperature durability, but in a high temperature environment, the transmittance of the polarizing plate may be significantly reduced due to polyeneization. In order to solve this problem, Patent Document 2 proposes a solution of using a transparent protective film having a saturated water absorption within a given range as a transparent protective film bonded to a polarizer and reducing the moisture content of the polarizing plate.
[0006] Patent Document 3 also relates to a polarizing plate with improved durability under high temperature or high humidity, and focuses on the moisture content of the polarizing plate and the moisture permeability of the protective film. In a high temperature environment, the interior of the polarizing plate reaches a high temperature and high humidity state, resulting in a large change in transmittance, polarization degree, image hue, etc., and a decrease in reliability as a polarizing plate. Therefore, the patent document proposes a solution of attaching a protective film with low moisture permeability while reducing the moisture content of the polarizer as much as possible.
[0007] Patent document 4 also relates to a polarizing plate with improved durability under high temperature or high humidity, or low temperature. It records that the polarizer will deteriorate due to ultraviolet rays and infrared rays; and the visual recognition of the liquid crystal display device (LCD) will deteriorate due to use at high temperature or high temperature and high humidity. In order to solve these problems, it is proposed to contain ultraviolet absorbers and infrared absorbers in the protective film of the polarizing film to prevent changes in transmittance.
[0008] Prior art literature
[0009] Patent Literature
[0010] Patent Document 1: Japanese Patent Application Publication No. 2003-29042
[0011] Patent Document 2: Japanese Patent Application Publication No. 2014-102353
[0012] Patent Document 3: Japanese Patent Application Publication No. 2002-90546
[0013] Patent Document 4: Japanese Patent Application Publication No. 2006-184883 Summary of the invention
[0014] Problems to be solved by the invention
[0015] Regarding optical display panels, especially polarizing film laminates used in optical display panels and polarizing films used in polarizing film laminates, "polyeneization", "discoloration", and "heat reddening" are known as problems that may occur in high temperature or high humidity environments.
[0016] Generally speaking, "polyeneization" refers to the phenomenon that the monomer transmittance of a polarizing film stack decreases due to being placed in a high temperature or high humidity environment. In addition, "discoloration" and "heat reddening" are also the phenomena that the orthogonal transmittance decreases when the polarizing film stack is arranged in an orthogonal Nicol manner and the orthogonal transmittances at wavelengths of 410nm and 700nm are measured due to being placed in a high temperature or high humidity environment. Among them, "discoloration" is particularly known as the phenomenon of increase in transmittance on the long wavelength side of about 700nm and the short wavelength side of about 410nm, and discoloration occurring under black display. On the other hand, "heat reddening" is particularly known as the phenomenon of increase in transmittance on the long wavelength side of about 700nm and change of color of the polarizing film to red.
[0017] Patent Document 1 mainly focuses on the problem of "decolorization", Patent Document 2 mainly focuses on the problem of "polyeneization", and Patent Document 3 mainly focuses on the problem of "red discoloration upon heating". It can be considered that the solutions proposed in each document are at least effective in solving their respective problems. However, the inventions recorded in each patent document may not be sufficient to solve these problems in a comprehensive manner. "Polyeneization", "decolorization", and "red discoloration upon heating" are all related to each other through iodine and moisture, and further through temperature and humidity that affect moisture. Based on this fact, the applicant of the present application has repeatedly conducted in-depth research and obtained the following insights: By adjusting the iodine concentration of the polarizing film and the moisture content of the polarizing film laminate, these problems can be solved in a comprehensive manner.
[0018] The applicant of the present application has further repeatedly conducted in-depth research and found more accurately that the ultraviolet light, visible light, and infrared light contained in sunlight promote "polyeneization", "bleaching", and "heat reddening", especially promote "polyeneization", and obtained the following insights: in addition to adjusting the iodine concentration of the polarizing film and the moisture content of the polarizing film laminate, the influence caused by sunlight is also suppressed, thereby being able to more effectively and comprehensively solve the problems of "polyeneization", "bleaching", and "heat reddening".
[0019] The purpose of the present invention is to suppress the influence of sunlight irradiation in addition to adjusting the iodine concentration of the polarizing film and the water content of the polarizing film laminate, thereby comprehensively solving the three problems of "polyeneization", "discoloration", and "heat reddening".
[0020] Solutions to the problem
[0021] In order to solve the above-mentioned problems, a polarizing film laminate of one embodiment of the present invention comprises: a polarizing film formed of a polyvinyl alcohol resin, and an optically transparent polarizing film protective film directly or through other optical films bonded to at least the visible side of the polarizing film, wherein the iodine concentration (wt.%) of the polarizing film is taken as the x-axis and the moisture content (g / m 2 ) as the y-axis, the polarizing film laminate has an iodine concentration and a moisture content within the following region, which is composed of a connected iodine concentration of 6.0 wt.% and a moisture content of 0.7 g / m 2 The first coordinate point and iodine concentration 1.8wt.% and moisture content 4.2g / m 2 The first line segment of the second coordinate point of the iodine concentration of 1.8wt.% and the water content of 5.1g / m 2 The second line segment of the third coordinate point, connecting the third coordinate point and the iodine concentration of 5.7wt.% and the water content of 2.6g / m2 The third line segment of the fourth coordinate point, connecting the fourth coordinate point and the iodine concentration of 7.0wt.% and the water content of 0.7g / m 2 The polarizing film protective film is a light absorbing layer with light absorption ability, and its transmittance to light at a wavelength of 380nm is less than 5%.
[0022] According to the polarizing film laminate of this embodiment, the problems of "polyeneization", "discoloration", and "reddening due to heating" can be solved comprehensively.
[0023] In the polarizing film laminate of the above embodiment, the polarizing film may have a thickness of 4 to 30 μm.
[0024] In addition, in another embodiment of the present invention, a polarizing film laminate comprises: a polarizing film formed of a polyvinyl alcohol resin, and an optically transparent polarizing film protective film directly or through other optical films bonded to at least the visible side of the polarizing film, wherein the iodine concentration (wt.%) of the polarizing film is taken as the x-axis, the moisture content (g / m 2 ) as the y-axis, the polarizing film laminate has an iodine concentration and a moisture content within the following region, which is composed of a connected iodine concentration of 4.5 wt.% and a moisture content of 1.9 g / m 2 The sixth coordinate point and iodine concentration 1.8wt.% and water content 4.2g / m 2 The sixth line segment of the second coordinate point of the iodine concentration of 1.8wt.% and the moisture content of 5.1g / m 2 The second line segment of the third coordinate point, connecting the third coordinate point and the iodine concentration of 4.5wt.% and the water content of 3.4g / m 2 The polarizing film protective film is surrounded by the seventh line segment of the seventh coordinate point and the eighth line segment connecting the sixth coordinate point and the seventh coordinate point. The polarizing film protective film is a light absorbing layer with light absorption ability, and the transmittance of light at a wavelength of 380nm is less than 5%.
[0025] In the polarizing film laminate of the above embodiment, the sixth coordinate point may have an iodine concentration of 4.0 wt.% and a water content of 2.4 g / m 2 The eighth coordinate point, the seventh coordinate point is iodine concentration 4.0wt.% and water content 3.7g / m 2 The ninth coordinate point.
[0026] Alternatively, the sixth coordinate point may be: the iodine concentration is 3.7 wt.% and the water content is 2.6 g / m 2The tenth coordinate point of , the seventh coordinate point mentioned above is the fourth coordinate point mentioned above.
[0027] In the polarizing film laminate of the above embodiment, the film thickness of the polarizing film may be 11 to 30 μm.
[0028] In addition, in another embodiment of the present invention, a polarizing film laminate comprises: a polarizing film formed of a polyvinyl alcohol resin, and an optically transparent polarizing film protective film directly or through other optical films bonded to at least the visible side of the polarizing film, wherein the iodine concentration (wt.%) of the polarizing film is taken as the x-axis, the moisture content (g / m 2 ) as the y-axis, the polarizing film laminate has an iodine concentration and a moisture content within the following region, which is composed of a connected iodine concentration of 6.0 wt.% and a moisture content of 0.7 g / m 2 The first coordinate point and iodine concentration 3.7wt.% and moisture content 2.6g / m 2 The ninth line segment of the tenth coordinate point connects the tenth coordinate point and the iodine concentration of 5.7wt.% and the water content of 2.6g / m 2 The tenth line segment of the fourth coordinate point, connecting the fourth coordinate point and the iodine concentration of 7.0wt.% and the water content of 0.7g / m 2 The polarizing film protective film is surrounded by the eleventh line segment of the fifth coordinate point and the fifth line segment connecting the first coordinate point and the fifth coordinate point. The polarizing film protective film is a light absorbing layer with light absorbing ability, and the transmittance of light at a wavelength of 380nm is less than 5%.
[0029] In the polarizing film laminate of the above embodiment, the polarizing film may have a thickness of 4 to 11 μm.
[0030] In the polarizing film laminate of the above embodiment, the transmittance of the polarizing film protective film at a wavelength of 390 nm is preferably 35% or less, and the transmittance of the polarizing film protective film at a wavelength of 400 nm is preferably 70% or less.
[0031] Moreover, in the polarizing film laminated body of the said embodiment, it is preferable that the said polarizing film contains zinc.
[0032] In addition, preferably, in the polarizing film laminate of the above embodiment, for a sample consisting of the polarizing film laminate and glass plates laminated on both sides of the polarizing film laminate via an adhesive, a black panel temperature of 89°C in an atmosphere of 30% RH in a wavelength range of 300 to 400 nm with a cumulative radiant illuminance of 100 W / m 2 After 200 hours of xenon light irradiation, the single body transmittance was -0.5 or more compared with the single body transmittance before irradiation.
[0033] Thereby, the problem of polyeneization can be effectively solved.
[0034] Preferably, in the polarizing film laminate of the above embodiment, for a sample consisting of the polarizing film laminate and glass plates laminated on both sides of the polarizing film laminate via an adhesive, a black panel temperature of 89°C in an atmosphere of 30% RH in a wavelength range of 300 to 400 nm with a cumulative radiant illuminance of 100 W / m 2 After irradiation with xenon light for 200 hours, the change in the cross transmittance at a wavelength of 410 nm was less than 1%, and the change in the cross transmittance at a wavelength of 700 nm was less than 5%.
[0035] Thereby, the problem of discoloration can be effectively solved.
[0036] Preferably, in the polarizing film laminate of the above embodiment, for a sample consisting of the polarizing film laminate and glass plates laminated on both sides of the polarizing film laminate via an adhesive, a black panel temperature of 89°C in an atmosphere of 30% RH in a wavelength range of 300 to 400 nm with a cumulative radiant illuminance of 100 W / m 2 After irradiation with xenon light for 200 hours, the amount of change in the orthogonal transmittance at a wavelength of 410 nm was 1% or more, and the amount of change in the orthogonal transmittance at a wavelength of 700 nm was less than 5%.
[0037] Thereby, the problem of reddening due to heating can be effectively solved.
[0038] Furthermore, in order to solve the above-mentioned problems, an optical display panel of one embodiment of the present invention is an optical display panel installed on the body of a power-driven vehicle, comprising: an optical display unit, a polarizing film stack as described in any of the above items joined to one side of the above-mentioned optical display unit directly or via other optical films, and an optically transparent cover plate arranged along the above-mentioned polarizing film stack on the side of the polarizing film stack opposite to the above-mentioned optical display unit, the above-mentioned optical display unit, the above-mentioned polarizing film stack and the above-mentioned transparent cover plate are bonded together by a transparent adhesive layer filled between them with no gaps.
[0039] In the optical display panel of the above embodiment, the transparent cover plate may have a function of a capacitive touch sensor.
[0040] In the optical display panel of the above embodiment, an ITO layer serving as a constituent element of a capacitive touch sensor may be provided between the transparent cover plate and the polarizing film laminate.
[0041] A polarizing film laminate with a transparent adhesive layer according to one embodiment of the present invention comprises: a polarizing film laminate comprising a polarizing film formed of a polyvinyl alcohol-based resin, and an optically transparent polarizing film protective film directly or via other optical films bonded to at least the visible side of the polarizing film; and a transparent adhesive layer laminated on the visible side closer to the polarizing film laminate, wherein the iodine concentration (wt.%) of the polarizing film is taken as the x-axis and the moisture content (g / m 2 ) as the y-axis, the polarizing film laminate with a transparent adhesive layer has an iodine concentration and a water content contained in the following region, which is composed of a connected iodine concentration of 6.0 wt.% and a water content of 0.7 g / m 2 The first coordinate point and iodine concentration 1.8wt.% and moisture content 4.2g / m 2 The first line segment of the second coordinate point of the iodine concentration of 1.8wt.% and the water content of 5.1g / m 2 The second line segment of the third coordinate point, connecting the third coordinate point and the iodine concentration of 5.7wt.% and the water content of 2.6g / m 2 The third line segment of the fourth coordinate point, connecting the fourth coordinate point and the iodine concentration of 7.0wt.% and the water content of 0.7g / m 2 The fourth line segment of the fifth coordinate point and the fifth line segment connecting the first coordinate point and the fifth coordinate point are surrounded by the transparent adhesive layer and the polarizing film protective film. In the transparent adhesive layer and the polarizing film protective film, at least the transparent adhesive layer is a light absorbing layer with light absorbing ability, and the transmittance of the laminated body of the transparent adhesive layer and the polarizing film protective film to light at a wavelength of 380nm is less than 5%.
[0042] Another embodiment of the present invention is a polarizing film laminate with a transparent adhesive layer, which comprises: a polarizing film laminate, which comprises a polarizing film formed of a polyvinyl alcohol resin, and an optically transparent polarizing film protective film directly or through other optical films bonded to the surface of the polarizing film opposite to the visible side; and a transparent adhesive layer laminated on the visible side of the polarizing film laminate, wherein the iodine concentration (wt.%) of the polarizing film is taken as the x-axis and the moisture content (g / m 2 ) as the y-axis, the polarizing film laminate with a transparent adhesive layer has an iodine concentration and a water content contained in the following region, which is composed of a connected iodine concentration of 6.0 wt.% and a water content of 0.7 g / m 2 The first coordinate point and iodine concentration 1.8wt.% and moisture content 4.2g / m 2 The first line segment of the second coordinate point of the iodine concentration of 1.8wt.% and the water content of 5.1g / m 2The second line segment of the third coordinate point, connecting the third coordinate point and the iodine concentration of 5.7wt.% and the water content of 2.6g / m 2 The third line segment of the fourth coordinate point, connecting the fourth coordinate point and the iodine concentration of 7.0wt.% and the water content of 0.7g / m 2 The transparent adhesive layer is surrounded by a fourth line segment of the fifth coordinate point and a fifth line segment connecting the first coordinate point and the fifth coordinate point. The transparent adhesive layer is a light absorbing layer with light absorbing ability. The transmittance of the transparent adhesive layer to light at a wavelength of 380nm is less than 5%.
[0043] A polarizing film assembly according to one embodiment of the present invention comprises: a polarizing film laminate, which comprises a polarizing film formed of a polyvinyl alcohol-based resin, and an optically transparent polarizing film protective film directly or via other optical films bonded to at least the visible side of the polarizing film; a transparent adhesive layer laminated on the visible side closer to the polarizing film laminate; and an optically transparent cover plate laminated on the visible side closer to the transparent adhesive layer, wherein the iodine concentration (wt.%) of the polarizing film is taken as the x-axis and the moisture content (g / m 2 ) as the y-axis, the polarizing film assembly has an iodine concentration and a water content within the following region, which is composed of a connected iodine concentration of 6.0 wt.% and a water content of 0.7 g / m 2 The first coordinate point and iodine concentration 1.8wt.% and moisture content 4.2g / m 2 The first line segment of the second coordinate point of the iodine concentration of 1.8wt.% and the water content of 5.1g / m 2 The second line segment of the third coordinate point, connecting the third coordinate point and the iodine concentration of 5.7wt.% and the water content of 2.6g / m 2 The third line segment of the fourth coordinate point, connecting the fourth coordinate point and the iodine concentration of 7.0wt.% and the water content of 0.7g / m 2 The fourth line segment of the fifth coordinate point and the fifth line segment connecting the first coordinate point and the fifth coordinate point are surrounded by the fourth line segment of the fifth coordinate point, and the fifth line segment connecting the first coordinate point and the fifth coordinate point. Among the polarizing film protective film, the transparent adhesive layer and the transparent cover plate, at least the transparent cover plate is a light absorbing layer with light absorbing ability, and the transmittance of the laminated body of the polarizing film protective film, the transparent adhesive layer and the transparent cover plate to light at a wavelength of 380nm is less than 5%.
[0044] Another embodiment of the polarizing film assembly of the present invention comprises: a polarizing film laminate, which comprises a polarizing film formed of a polyvinyl alcohol-based resin, and an optically transparent polarizing film protective film directly or through other optical films bonded to the surface of the polarizing film opposite to the visible side; a transparent adhesive layer laminated on the visible side of the polarizing film laminate; and an optically transparent cover plate laminated on the visible side of the polarizing film laminate, wherein the iodine concentration (wt.%) of the polarizing film is taken as the x-axis and the moisture content (g / m 2 ) as the y-axis, the polarizing film assembly has an iodine concentration and a water content within the following region, which is composed of a connected iodine concentration of 6.0 wt.% and a water content of 0.7 g / m 2 The first coordinate point and iodine concentration 1.8wt.% and moisture content 4.2g / m 2 The first line segment of the second coordinate point of the iodine concentration of 1.8wt.% and the water content of 5.1g / m 2 The second line segment of the third coordinate point, connecting the third coordinate point and the iodine concentration of 5.7wt.% and the water content of 2.6g / m 2 The third line segment of the fourth coordinate point, connecting the fourth coordinate point and the iodine concentration of 7.0wt.% and the water content of 0.7g / m 2 The fourth line segment of the fifth coordinate point and the fifth line segment connecting the first coordinate point and the fifth coordinate point are surrounded by the transparent adhesive layer and the transparent cover plate, and at least the transparent cover plate is a light absorbing layer with light absorbing ability, and the transmittance of the stacked body of the transparent adhesive layer and the transparent cover plate to light at a wavelength of 380nm is less than 5%.
[0045] Effects of the Invention
[0046] According to the present invention, in addition to adjusting the iodine concentration of the polarizing film and the water content of the polarizing film laminate, the influence caused by sunlight irradiation is also suppressed, thereby comprehensively solving the problems of "polyeneization", "discoloration", and "heat reddening". BRIEF DESCRIPTION OF THE DRAWINGS
[0047] Figure 1 is a schematic diagram showing the layer structure of an optical display panel.
[0048] Figure 2 This is a diagram for explaining an example of a method for producing a polarizing film.
[0049] Figure 3 It is a figure which shows the layer structure example of the polarizing film protective film located on the visible side.
[0050] Figure 4This is a diagram showing a calibration curve for calculating the iodine concentration of a polarizing film.
[0051] Figure 5 It is a diagram showing a structure used for reliability test.
[0052] Figure 6 This is a graph in which the results of Examples and Comparative Examples are plotted, with Examples as the main focus.
[0053] Figure 7 This is a graph in which the results of Examples and Comparative Examples are plotted, with Comparative Examples being the main focus.
[0054] Explanation of symbols
[0055] 1 Optical display panel
[0056] 10 Optical display unit
[0057] 11. Transparent adhesive
[0058] 12 Polarizing film laminate
[0059] 13 Transparent adhesive
[0060] 14 Transparent cover
[0061] 120 polarizing film
[0062] 121 Polarizing film protective film with light absorption ability
[0063] 122 Polarizing film protective film DETAILED DESCRIPTION
[0064] Hereinafter, a preferred embodiment of the present invention will be described with reference to the accompanying drawings. For the convenience of description, only the preferred embodiment is shown, but the present invention is of course not limited to this.
[0065] The present invention is directed to an optical display panel, such as an optical display panel mounted on the body of a car, a train, an airplane, or other powered vehicle that is powered, and a polarizing film laminate used for the optical display panel. Here, "mounted on the body" does not necessarily refer only to the case where the optical display panel or polarizing film laminate is fixed to the body, but also includes the case where they are freely mounted or brought into a powered vehicle, such as an optical display panel or polarizing film laminate used in a smart phone. In other words, "mounted on the body" includes all situations where the optical display panel or polarizing film laminate is used together with a powered vehicle and may be exposed to a high temperature or high humidity environment.
[0066] 1. Optical display panel
[0067] Figure 1An example of the layer structure of the optical display panel 1 is shown in a schematic diagram. The optical display panel 1 includes at least: an optical display unit 10, a polarizing film laminate 12 laminated on one side 10a (visible side) of the optical display unit 10, and an optically transparent cover plate 14 arranged along the polarizing film laminate 12 on the side opposite to the optical display unit 10, i.e., the visible side. Between the optical display unit 10 and the polarizing film laminate 12, a transparent adhesive layer formed by a transparent adhesive (PSA) 11 is used to bond them together without a gap. Similarly, between the cover plate 14 and the polarizing film laminate 12, a transparent adhesive layer formed by a transparent adhesive (OCA) 13 laminated on the visible side closer to the polarizing film laminate 12 is used to bond them together without a gap, thereby forming a polarizing film assembly 19 including the cover plate 14, the transparent adhesive 13, and the polarizing film laminate 12. On the other side 10b of the optical display unit 10, another polarizing film laminate 17 is arranged via a transparent adhesive (PSA) 16. It should be noted that in this specification, unless otherwise specified, the term "bonding" includes adhesion (pressure-sensitive bonding). The optical display unit 10 and the polarizing film laminate 12 can also be directly bonded together by the transparent adhesive 11, but can also be bonded together via other optical films (not shown) such as a phase difference film and a viewing angle compensation film as needed.
[0068] 1-1. Optical display unit
[0069] Examples of the optical display unit 10 include a liquid crystal unit and an organic EL unit.
[0070] As the organic EL unit, an organic EL unit in which a transparent electrode, an organic light-emitting layer and a metal electrode are sequentially stacked on a transparent substrate to form a light-emitting body (organic electroluminescent light-emitting body) can be suitably used. The organic light-emitting layer is a laminate of various organic thin films, and can adopt various layer structures, including, for example: a laminate of a hole injection layer made of a triphenylamine derivative and a light-emitting layer made of a fluorescent organic solid such as anthracene, a laminate of these light-emitting layers and an electron injection layer made of a perylene derivative, or a laminate of a hole injection layer, a light-emitting layer and an electron injection layer.
[0071] As the liquid crystal cell, any of a reflective liquid crystal cell utilizing external light, a transmissive liquid crystal cell utilizing light from a light source such as the backlight 18, and a semi-transmissive and semi-reflective liquid crystal cell utilizing both light from the outside and light from the light source can be used. In the case where the liquid crystal cell is a liquid crystal cell utilizing light from a light source, such as Figure 1As shown, a polarizing film laminate 17 may also be arranged on the side opposite to the visible side of the optical display unit (liquid crystal unit) 10, and a light source 18 such as a backlight may be arranged. The polarizing film laminate 17 on the light source side and the liquid crystal unit 10 are bonded together via a layer of a suitable transparent adhesive 16. As a driving mode of the liquid crystal unit, any type of mode such as VA mode, IPS mode, TN mode, STN mode, bend orientation (π type) may be adopted.
[0072] 1-2. Cover
[0073] As examples of the cover plate 14, a transparent plate (window layer), a touch panel, etc. can be cited. As a transparent plate, a transparent plate with suitable mechanical strength and thickness can be used. As such a transparent plate, a transparent resin plate such as an acrylic resin or a polycarbonate resin, or a glass plate, etc. can be used. For example, a low-reflection film (not shown) can be used to apply a low-reflection treatment to the surface of the cover plate 14. As a touch panel, various touch panels such as a resistive film method, an electrostatic capacitance method, an optical method, an ultrasonic method, etc., a glass plate with a touch sensor function, a transparent resin plate, etc. can be used.
[0074] The cover plate 14 may contain an ultraviolet absorber to form a light absorbing layer having light absorbing ability. In other words, the transmittance of the cover plate 14 to ultraviolet rays may be set to a desired value. For example, the cover plate 14 is formed of a transparent resin plate such as an acrylic resin or a polycarbonate resin, or a glass plate, and when it is made, ultraviolet absorbers such as benzotriazoles, benzophenones, phenyl salicylates, and triazines may be used. As benzotriazole ultraviolet absorbers, for example, 2-(5-methyl-2-hydroxyphenyl)benzotriazole, 2-(2H-benzotriazole-2-yl)-p-cresol, 2-(2H-benzotriazole-2-yl)-4,6-di-tert-amylphenol, 2-(2'-hydroxy-5'-methacryloyloxyethylphenyl)-2H-benzotriazole, etc. may be used. Examples of the benzophenone-based ultraviolet absorber include 2-hydroxy-4-octyloxybenzophenone, 2,4-dihydroxybenzophenone, 2-hydroxy-4-methoxy-4'-chlorobenzophenone, 2,2-dihydroxy-4-methoxybenzophenone, and 2,2-dihydroxy-4,4'-dimethoxybenzophenone. Examples of the phenyl salicylate-based ultraviolet absorber include p-tert-butylphenyl salicylate. As the triazine type ultraviolet absorber, for example, 2,4-diphenyl-6-(2-hydroxy-4-methoxyphenyl)-1,3,5-triazine, 2,4-diphenyl-6-(2-hydroxy-4-ethoxyphenyl)-1,3,5-triazine, 2,4-diphenyl-(2-hydroxy-4-propoxyphenyl)-1,3,5-triazine, 2,4-diphenyl-(2-hydroxy-4-butoxyphenyl)-1,3,5-triazine, 2,4-diphenyl-6-(2-hydroxy-4-butoxyphenyl)-1,3,5-triazine, 2,4-diphenyl-6-(2-hydroxy-4-ethoxyphenyl)-1,3,5-triazine, 2,4-diphenyl-(2-hydroxy-4-propoxyphenyl)-1,3,5-triazine, 2,4-diphenyl ...propoxyphenyl)-1,3,5-triazine, 2,4-diphenyl-6-(2-hydroxy-4-ethoxyphenyl)-1,3,5-triazine, 2,4-diphenyl-(2-hydroxy-4-propoxyphenyl)-1,3,5-triazine, 2 The cover plate 14 is used as a light absorbing layer by mixing an ultraviolet absorber such as 2-hydroxy-4-hexyloxyphenyl)-1,3,5-triazine, 2,4-diphenyl-6-(2-hydroxy-4-octyloxyphenyl)-1,3,5-triazine, 2,4-diphenyl-6-(2-hydroxy-4-dodecyloxyphenyl)-1,3,5-triazine, 2,4-diphenyl-6-(2-hydroxy-4-benzyloxyphenyl)-1,3,5-triazine, and 2,4-diphenyl-6-(2-hydroxy-4-butoxyethoxyphenyl)-1,3,5-triazine into a transparent resin. By providing a light absorbing layer, the ultraviolet transmittance of the polarizing film assembly 19 including the polarizing film laminate 12 can be set to a desired value, thereby more effectively and comprehensively solving the problems of "polyeneization", "discoloration", and "heat reddening". When only the cover plate 14 is used as the light absorbing layer, the transmittance at a wavelength of 380 nm is preferably 5% or less, more preferably 3% or less, and further preferably 2% or less, and the lower limit thereof is, for example, 0.1% or more or 1% or more.The transmittance at a wavelength of 390 nm is preferably 35% or less, more preferably 30% or less, and further preferably 28% or less, and its lower limit is, for example, 10% or more, 20% or more, or 25% or more. The transmittance at a wavelength of 400 nm is preferably 70% or less, more preferably 68% or less, and its lower limit is, for example, 50% or more, 60% or more, or 65% or more. The transmittance at a wavelength of 420 nm is preferably 90% or less, and its lower limit is, for example, 80% or more, or 85% or more. These transmittances represent the transmittances of the cover plate 14 in the initial state. It should be noted that, in addition to the ultraviolet absorber, an infrared absorber such as a phthalocyanine light absorber, a naphthalocyanine light absorber, a polymethine light absorber, a diphenylmethane light absorber, a triphenylmethane light absorber, a quinone light absorber, or an azo light absorber may be mixed.
[0075] When a capacitive touch panel is used as the cover plate 14, a front transparent plate made of glass or a transparent resin plate is preferably provided on the side closer to the visible side than the touch panel. In this case, the transparent adhesive 13 joining the cover plate 14 and the polarizing film laminate 12 is provided with an ITO layer (not shown) which is a component of the capacitive touch sensor.
[0076] 1-3. Transparent adhesive
[0077] As transparent adhesives 11, 13, and 16, various adhesives such as those disclosed in Japanese Patent No. 6071459 can be suitably used. For example, a (meth) acrylic adhesive can be used, and a curing adhesive that does not contain (meth) acrylic acid can also be used. As an example of the latter, an isoprene-based UV-curing adhesive can be suitably used. In addition to isoprene, the isoprene-based UV-curing adhesive can also contain an isoprene derivative as a monomer component. The adhesive can also contain monomer components other than isoprene monomers. As a monomer component, a (meth) acrylic acid derivative such as (meth) acrylic acid ester can be contained. It should be noted that in order to suppress the reduction in transmittance caused by the polyeneization of polyvinyl alcohol, it is effective to reduce the content of the acid component in the transparent adhesives 11, 13, and 16.
[0078] Transparent adhesives 11, 13, 16, for example, transparent adhesive 13 (transparent adhesive layer) stacked on the visible side closer to the polarizing film stack 12 can contain ultraviolet absorbers to form a light absorbing layer with light absorbing ability. In other words, the transmittance of the transparent adhesive to ultraviolet rays can be set to a desired value. For example, when a transparent adhesive is formed by a (meth) acrylic adhesive, ultraviolet absorbers such as benzotriazoles, benzophenones, phenyl salicylates, and triazines can be listed in its preparation. As benzotriazole ultraviolet absorbers, for example, 2-(5-methyl-2-hydroxyphenyl)benzotriazole, 2-(2H-benzotriazole-2-yl)p-cresol, 2-(2H-benzotriazole-2-yl)-4,6-di-tert-amylphenol, 2-(2'-hydroxy-5'methacryloyloxyethylphenyl)-2H-benzotriazole, etc. can be listed. Examples of the benzophenone-based ultraviolet absorbers include 2-hydroxy-4-octyloxybenzophenone, 2,4-dihydroxybenzophenone, 2-hydroxy-4-methoxy-4'-chlorobenzophenone, 2,2-dihydroxy-4-methoxybenzophenone, and 2,2-dihydroxy-4,4'-dimethoxybenzophenone. Examples of the phenyl salicylate-based ultraviolet absorbers include p-tert-butylphenyl salicylate. As the triazine type ultraviolet absorber, for example, 2,4-diphenyl-6-(2-hydroxy-4-methoxyphenyl)-1,3,5-triazine, 2,4-diphenyl-6-(2-hydroxy-4-ethoxyphenyl)-1,3,5-triazine, 2,4-diphenyl-(2-hydroxy-4-propoxyphenyl)-1,3,5-triazine, 2,4-diphenyl-(2-hydroxy-4-butoxyphenyl)-1,3,5-triazine, 2,4-diphenyl-6-(2-hydroxy-4-butoxyphenyl)-1,3,5-triazine, 2,4-diphenyl-6-(2 -hydroxy-4-hexyloxyphenyl)-1,3,5-triazine, 2,4-diphenyl-6-(2-hydroxy-4-octyloxyphenyl)-1,3,5-triazine, 2,4-diphenyl-6-(2-hydroxy-4-dodecyloxyphenyl)-1,3,5-triazine, 2,4-diphenyl-6-(2-hydroxy-4-benzyloxyphenyl)-1,3,5-triazine, 2,4-diphenyl-6-(2-hydroxy-4-butoxyethoxyphenyl)-1,3,5-triazine and other ultraviolet absorbers are mixed in the transparent resin, so that the transparent adhesive is used as a light absorbing layer. By providing such a light absorbing layer, the transmittance of ultraviolet rays of the polarizing film laminate 12 with a transparent adhesive layer or the polarizing film assembly 19 including the polarizing film laminate 12 can be set to a desired value, so that the problems of "polyeneization", "discoloration", and "heat reddening" can be solved more effectively and comprehensively.When only the transparent adhesive 13 is used as the light absorbing layer, for example, the transmittance at a wavelength of 380 nm is preferably 5% or less, more preferably 3% or less, and further preferably 2% or less, and its lower limit is, for example, 0.1% or more, or 1% or more. The transmittance at a wavelength of 390 nm is preferably 35% or less, more preferably 30% or less, and further preferably 28% or less, and its lower limit is, for example, 10% or more, 20% or more, or 25% or more. The transmittance at a wavelength of 400 nm is preferably 70% or less, more preferably 68% or less, and its lower limit is, for example, 50% or more, 60% or more, or 65% or more. The transmittance at a wavelength of 420 nm is preferably 90% or less, and its lower limit is, for example, 80% or more, or 85% or more. These transmittances represent the transmittances of the transparent adhesive in the initial state. In addition to the ultraviolet absorber, an infrared absorber such as a phthalocyanine light absorber, a naphthalocyanine light absorber, a polymethine light absorber, a diphenylmethane light absorber, a triphenylmethane light absorber, a quinone light absorber, or an azo light absorber may be mixed.
[0079] 2. Polarizing film laminate
[0080] The polarizing film laminate 12 includes at least: a polarizing film 120, and a polarizing film protective film 121 bonded to at least the visible side of the polarizing film 120. The polarizing film laminate 12 includes at least a polarizing film 120, and a polarizing film protective film 121 bonded to at least the visible side of the polarizing film 120. The polarizing film laminate 12 may further include a polarizing film protective film 122 on the side of the polarizing film 120 opposite to the visible side. In addition to using the cover plate 14 and / or the transparent adhesive 13 as a light absorbing layer, the polarizing film protective film 121 may also function as a light absorbing layer, or instead of this method, the polarizing film protective film 121 may function as a light absorbing layer. By providing a light absorbing layer, the transmittance of ultraviolet rays of the polarizing film laminate 12 itself can be set to a desired value, thereby more effectively and comprehensively solving the problems of "polyeneization", "discoloration", and "heat reddening". Although not particularly shown, other optical films may be provided between the polarizing film 120 and the polarizing film protective films 121 and 122 .
[0081] The present invention aims to comprehensively solve the problems caused by the use environment of high temperature or high humidity and the irradiation of sunlight, especially the problems of "polyeneization", "bleaching" and "heat reddening", and in particular focuses on the iodine concentration (wt.%) of the polarizing film 120 and the moisture content (g / m 2 ). These values can be adjusted, for example, during the manufacture of a polarizing film or a polarizing film laminate.
[0082] 2-1.Polarizing film
[0083] Polarizing film 120 is made of a polyvinyl alcohol (PVA) resin film containing iodine. As a material suitable for PVA-type films of polarizing film, PVA or its derivatives can be used. As derivatives of PVA, in addition to polyvinyl formal, polyvinyl acetal, etc., derivatives modified by olefins such as ethylene and propylene, unsaturated carboxylic acids such as acrylic acid, methacrylic acid, crotonic acid, or their alkyl esters, acrylamide, etc. can also be listed. PVA generally uses PVA with a degree of polymerization of about 1000 to 10000 and a saponification degree of about 80 to 100 mol%. PVA-type films made of these materials tend to contain moisture easily.
[0084] The PVA film may also contain additives such as plasticizers. Examples of the plasticizer include polyols and condensates thereof, such as glycerol, diglycerol, triglycerol, ethylene glycol, propylene glycol, and polyethylene glycol. The amount of the plasticizer is not particularly limited, but is preferably 20% by weight or less in the PVA film.
[0085] 2-1-1. Manufacturing of polarizing film
[0086] When manufacturing a polarizing film having a thickness of 6 μm or more, for example, a dyeing treatment of dyeing the PVA film with iodine and a stretching treatment of stretching the PVA film in at least one direction are performed. Generally, a series of treatments including swelling, dyeing, cross-linking, stretching, washing and drying can be performed on the PVA film.
[0087] The swelling treatment can be performed, for example, by immersing the PVA film in a swelling bath (water bath). By this treatment, the PVA film can be swollen while cleaning the dirt and anti-blocking agent on the surface of the PVA film, thereby preventing uneven dyeing and the like. Glycerin, potassium iodide, etc. can also be appropriately added to the swelling bath. The temperature of the swelling bath is, for example, about 20 to 60° C., and the immersion time in the swelling bath is, for example, about 0.1 to 10 minutes.
[0088] The dyeing treatment can be performed, for example, by immersing the PVA film in an iodine solution. The iodine solution is usually an iodine aqueous solution, and contains potassium iodide as iodine and a dissolving aid. The iodine concentration is, for example, about 0.01 to 1% by weight, preferably 0.02 to 0.5% by weight. The potassium iodide concentration is, for example, about 0.01 to 10% by weight, preferably 0.02 to 8% by weight.
[0089] During the dyeing treatment, the temperature of the iodine solution is, for example, about 20 to 50° C., preferably 25 to 40° C. The immersion time is, for example, about 10 to 300 seconds, preferably 20 to 240 seconds. During the iodine dyeing treatment, the concentration of the iodine solution, the immersion temperature of the PVA film in the iodine solution, the immersion time, and other conditions are adjusted so that the iodine content and potassium content in the PVA film are within the above ranges.
[0090] The cross-linking treatment can be carried out, for example, by immersing the PVA film after iodine dyeing in a treatment bath containing a cross-linking agent. As a cross-linking agent, any appropriate cross-linking agent can be used. As specific examples of cross-linking agents, boric compounds such as boric acid and borax, glyoxal, glutaraldehyde, etc. can be cited. These cross-linking agents can be used alone or in combination. As a solvent for the solution of the cross-linking bath, water is usually used, but an organic solvent compatible with water can also be appropriately added. Relative to 100 parts by weight of the solvent, the cross-linking agent is used in a ratio of, for example, 1 to 10 parts by weight. Preferably, the solution of the cross-linking bath further contains an auxiliary agent such as iodide. The concentration of the auxiliary agent is preferably 0.05 to 15% by weight, and more preferably 0.5 to 8% by weight. The temperature of the cross-linking bath is, for example, about 20 to 70°C, and preferably 40 to 60°C. The immersion time in the cross-linking bath is, for example, about 1 second to 15 minutes, and preferably 5 seconds to 10 minutes.
[0091] Stretching treatment is a treatment in which the PVA film is stretched in at least one direction. Generally speaking, the PVA film is uniaxially stretched in the conveying direction (length direction). There is no particular limitation on the stretching method, and any method of wet stretching method and dry stretching method can be adopted. In the case of wet stretching method, the PVA film is stretched to a given ratio in a treatment bath. As a solution of the stretching bath, a solution obtained by adding compounds necessary for various treatments to solvents such as water or organic solvents (such as ethanol) can be appropriately used. As a dry stretching method, for example, an inter-roll stretching method, a heated roller stretching method, a compression stretching method, etc. can be cited. In the manufacture of polarizing film, stretching treatment can be carried out in any stage. Specifically, it can be carried out simultaneously with swelling, dyeing, and cross-linking, or it can be carried out at any time before and after the above-mentioned treatments. In addition, stretching can also be carried out in multiple stages. The cumulative stretching ratio of the PVA film is, for example, more than 5 times, preferably about 5 to 7 times.
[0092] The PVA-based film (stretched film) subjected to the above-mentioned respective treatments is subjected to water washing treatment and drying treatment according to a conventional method.
[0093] The water washing treatment can be carried out, for example, by immersing the PVA film in a water washing bath. The water washing bath can be pure water or an aqueous solution of an iodide (e.g., potassium iodide, sodium iodide, etc.). The concentration of the iodide aqueous solution is preferably 0.1 to 10% by weight. An auxiliary agent such as zinc sulfate or zinc chloride can also be added to the iodide aqueous solution.
[0094] The water washing temperature is, for example, 5 to 50° C., preferably 10 to 45° C., and more preferably 15 to 40° C. The immersion time is, for example, about 10 to 300 seconds, preferably 20 to 240 seconds. The water washing treatment may be performed only once, or may be performed multiple times as needed. When multiple water washing treatments are performed, the type and concentration of the additives contained in the water washing bath used for each treatment may be appropriately adjusted.
[0095] The drying treatment of the PVA-based film can be performed by any appropriate method (for example, natural drying, air drying, and heat drying).
[0096] 2-1-2. Manufacturing of polarizing film
[0097] Polarizing films with a film thickness of less than 6 μm can be manufactured, for example, by the manufacturing method disclosed in Japanese Patent Gazette No. 4751481. The manufacturing method includes: a laminate preparation process in which a PVA-type resin layer is formed on a thermoplastic substrate; a stretching process in which the PVA-type resin layer and the thermoplastic resin substrate are stretched integrally; a dyeing process in which a dichroic substance is adsorbed on the PVA resin layer, and the like. Insolubilization treatment and cross-linking treatment, drying treatment, cleaning treatment, and the like of the PVA-type resin layer can also be adopted as needed. The stretching treatment can be implemented before or after the dyeing treatment. In addition, any stretching method of stretching in a gas atmosphere and stretching in an aqueous solution such as a boric acid aqueous solution can be adopted. In addition, the stretching can be a one-stage stretching or a multi-stage stretching of more than two stages.
[0098] Reference Figure 2 Here, an example of a method for producing a polarizing film is described. Here, a PVA-based resin layer formed on a resin substrate is stretched integrally with the resin substrate to produce a polarizing film.
[0099] [Laminate production process (A)]
[0100] First, a non-crystalline ester thermoplastic resin substrate having a glass transition temperature of 75°C and a thickness of 200 μm, for example, isophthalic acid copolymerized polyethylene terephthalate (hereinafter referred to as "non-crystalline PET") 6 having a glass transition temperature of 75°C and a PVA aqueous solution having a concentration of 4 to 5% by weight obtained by dissolving PVA powder having a polymerization degree of 1000 or more and a saponification degree of 99% or more in water is prepared. Next, in a laminate production device 20 having a coating mechanism 21, a drying mechanism 22, and a surface modification treatment device 23, the PVA aqueous solution is coated on the non-crystalline PET substrate 6, and dried at a temperature of 50 to 60°C, and a PVA layer 2 having a glass transition temperature of 80°C and a thickness of 7 μm is formed on the PET substrate 6. In this way, a laminate 7 including a 7 μm thick PVA layer can be produced. At this time, by corona-treating the surface of the amorphous PET substrate 6 using the surface modification treatment device 23, the adhesion between the amorphous PET substrate 6 and the PVA layer 2 formed thereon can be improved.
[0101] Next, the laminate 7 including the PVA layer was subjected to the following treatment including two-step stretching treatment of auxiliary stretching in an air atmosphere and stretching in a boric acid aqueous solution, thereby finally producing a polarizing film having a thickness of 3 μm.
[0102] [Assisted stretching treatment in gas atmosphere (B)]
[0103] In the first stage of the in-air auxiliary stretching treatment (B), the laminate 7 including the 7 μm thick PVA layer 2 is stretched integrally with the PET substrate 6 to generate a "stretched laminate 8" including the 5 μm thick PVA layer 2. Specifically, in the in-air auxiliary stretching treatment device 30 equipped with a stretching mechanism 31 in the oven 33, the laminate 7 including the 7 μm thick PVA layer 2 is set in the stretching mechanism 31 of the oven 33 set to a stretching temperature environment of 130°C, and the free end uniaxial stretching is performed in such a way that the stretching ratio reaches 1.8 times to generate the stretched laminate 8. In this stage, the roll 8' of the stretched laminate 8 can be manufactured by the winding device 32 also provided in the oven 30.
[0104] [Dyeing treatment (C)]
[0105] Next, by dyeing treatment (C), a colored laminate 9 is produced in which iodine, which is a dichroic substance, is adsorbed on a 5 μm thick PVA layer 2 in which PVA molecules are oriented. Specifically, in a dyeing device 40 having a dye bath 42 of a dyeing liquid 41, a stretched laminate 8 is continuously unloaded from a continuous unloading device 43 equipped with a roll 8' provided in the dyeing device 40, and is immersed in a dyeing liquid 41 containing iodine and potassium iodide at a liquid temperature of 30° C. for an arbitrary period of time, and the monomer transmittance of the PVA layer constituting the polarizing film finally produced is made to be 40 to 44%, thereby producing a colored laminate 9 in which iodine is adsorbed on the oriented PVA layer 2 of the stretched laminate 8.
[0106] In this treatment, in order to prevent the dyeing liquid 41 from dissolving the PVA layer 2 contained in the stretched laminate 8, water is used as a solvent and the iodine concentration is set to 0.30 wt%. In addition, the concentration of potassium iodide in the dyeing liquid 41 for dissolving iodine in water is set to 2.1 wt%. The ratio of the concentration of iodine to potassium iodide is 1 to 7. More specifically, the stretched laminate 8 is immersed in the dyeing liquid 41 with an iodine concentration of 0.30 wt% and a potassium iodide concentration of 2.1 wt% for 60 seconds, thereby generating a colored laminate 9 in which iodine is adsorbed on the PVA layer 2 with a thickness of 5 μm after the PVA molecules are oriented.
[0107] [Stretching treatment in a boric acid aqueous solution (D)]
[0108] The colored laminate 9 including the iodine-oriented PVA layer 2 is further stretched by the second stage of the boric acid aqueous solution stretching treatment, thereby generating an optical film laminate 60 including a 3 μm thick PVA layer constituting a polarizing film and oriented with iodine. Specifically, in the boric acid aqueous solution stretching treatment device 50 having a boric acid bath 52 of the boric acid aqueous solution 51 and a stretching mechanism 53, the colored laminate 9 continuously discharged from the dyeing device 40 is immersed in the boric acid aqueous solution 51 containing boric acid and potassium iodide and set to a stretching temperature environment of 65°C. Next, the free-end uniaxial stretching is performed in the stretching mechanism 53 provided in the boric acid aqueous solution treatment device 50 so as to achieve a stretching ratio of 3.3 times, thereby generating an optical film laminate 60 including a 3 μm thick PVA layer.
[0109] [Cleaning treatment (G)]
[0110] Next, the optical film laminate 60 including the polarizing film is preferably directly sent to the cleaning process (G). The purpose of the cleaning process (G) is to wash away the unnecessary residues attached to the surface of the polarizing film by the cleaning liquid 81 of the cleaning device 80. However, the cleaning process (G) can also be omitted, and the optical film laminate 60 including the polarizing film taken out can be directly sent to the drying process (H).
[0111] [Drying treatment (H)]
[0112] The cleaned optical film laminate 60 is sent to a drying process (H) and dried there. Next, the dried optical film laminate 60 is rolled up into a continuous web of optical film laminate 60 by a winding device 91 provided together with the drying device 90, thereby generating a roll of the optical film laminate 60 including the polarizing film. As the drying process (H), any appropriate method may be adopted, such as natural drying, air drying, and heating drying. For example, in the drying device 90 of the oven, hot air at 60°C is used for drying for 240 seconds.
[0113] 2-1-3. Others
[0114] The polarizing film preferably contains zinc. By making the polarizing film contain zinc, there is a tendency to suppress the decrease in transmittance and hue degradation of the polarizing film laminate after the heating test. When the polarizing film contains zinc, the content of zinc in the polarizing film is preferably 0.002 to 2% by weight, and more preferably 0.01 to 1% by weight.
[0115] Preferably, the polarizing film further contains sulfate ions. By making the polarizing film contain sulfate ions, there is a tendency to suppress the decrease in the transmittance of the polarizing film laminate after the heating test. In the case where the polarizing film contains sulfate ions, the content of sulfate ions in the polarizing film is preferably 0.02 to 0.45% by weight, more preferably 0.05 to 0.35% by weight, and further preferably 0.1 to 0.25% by weight. It should be noted that the content of sulfate ions in the polarizing film can be calculated based on the sulfur atom content.
[0116] In order to include zinc in the polarizing film, it is preferred to perform zinc impregnation treatment in the production process of the polarizing film. In addition, in order to include sulfate ions in the polarizing film, it is preferred to perform sulfate ion treatment in the production process of the polarizing film.
[0117] The zinc impregnation treatment can be carried out, for example, by immersing the PVA film in a zinc salt solution. As the zinc salt, an inorganic chlorine compound in an aqueous solution of zinc halides such as zinc chloride and zinc iodide, zinc sulfate, zinc acetate, etc. is preferred. In addition, various zinc complexes can also be used in the zinc impregnation treatment. In addition, when the zinc salt solution uses an aqueous solution containing potassium ions and iodide ions using potassium iodide, etc., it is easy to impregnate the zinc ions, so it is preferred. The potassium iodide concentration in the zinc salt solution is preferably set to about 0.5 to 10% by weight, and more preferably set to 1 to 8% by weight.
[0118] Sulfate ion treatment can be performed, for example, by immersing the PVA film in an aqueous solution containing a metal sulfate. As the metal sulfate, the following metal sulfate is preferred: it is easy to separate into sulfate ions and metal ions in the treatment solution, and it is easy to introduce the metal sulfate into the PVA film in the form of ions. For example, as the type of metal forming the metal sulfate, alkali metals such as sodium and potassium; alkaline earth metals such as magnesium and calcium; and transition metals such as cobalt, nickel, zinc, chromium, aluminum, copper, manganese, and iron can be listed.
[0119] In the manufacture of polarizing film, the above-mentioned zinc infiltration treatment and sulfate ion treatment can be carried out at any stage. That is, the zinc infiltration treatment and sulfate ion treatment can be carried out before the dyeing treatment, or after the dyeing treatment. The zinc infiltration treatment and sulfate ion treatment can also be carried out simultaneously. Preferably, zinc sulfate is used as the above-mentioned zinc salt and the above-mentioned metal sulfate salt, and the PVA-type film is immersed in a treatment bath containing zinc sulfate, so that the zinc infiltration treatment and sulfate ion treatment are carried out simultaneously. In addition, the above-mentioned zinc salt and the above-mentioned metal sulfate salt can also be coexisted in the dyeing solution in advance, and the zinc infiltration treatment and / or sulfate ion treatment can be carried out simultaneously with the dyeing treatment. The zinc infiltration treatment and sulfate ion treatment can also be carried out simultaneously with stretching.
[0120] 2-2. Polarizing film protective film
[0121] 2-2-1. Polarizing film protective film on the side opposite to the visible side
[0122] exist Figure 1 In the polarizing film laminate 12, as a material constituting the polarizing film protective film 122 located on the side opposite to the visible side relative to the polarizing film 120, for example, a thermoplastic resin having excellent transparency, mechanical strength and thermal stability can be cited. Specific examples of such thermoplastic resins include cellulose resins such as triacetyl cellulose, polyester resins, polyethersulfone resins, polysulfone resins, polycarbonate resins, polyamide resins, polyimide resins, polyolefin resins, (meth) acrylic resins, cyclic polyolefin resins (norbornene resins), polyarylate resins, polystyrene resins, PVA resins, and mixtures thereof.
[0123] The polarizing film protection film 122 may also function as a phase difference film.
[0124] The thickness of polarizing film protective film 122 can be appropriately adjusted for the purpose of adjusting the moisture content of the polarizing film laminate, and is preferably about 1 to 500 μm, more preferably 2 to 300 μm, and even more preferably 5 to 200 μm in view of strength, workability such as handling, and thinness.
[0125] Polarizing film protective film 122 may contain one or more optional additives. Examples of the additives include ultraviolet absorbers, antioxidants, lubricants, plasticizers, mold release agents, anti-coloring agents, flame retardants, nucleating agents, antistatic agents, pigments, and colorants.
[0126] 2-2-2. Polarizing film protective film on the visible side
[0127] exist Figure 1 In the polarizing film laminate 12, the polarizing film protective film 121 located closer to the visible side than the polarizing film 120 is formed in the form of a light absorbing layer having light absorbing ability. In other words, its transmittance to ultraviolet rays is set to a desired value. For example, by containing an ultraviolet absorber, the polarizing film protective film 121 can be formed as a light absorbing layer having light absorbing ability, but as long as the transmittance to ultraviolet rays can be set to a desired value, it is not necessary to use an ultraviolet absorber. For example, an ultraviolet absorption filter can be used instead of an ultraviolet absorber to set the desired transmittance. In the case where only the polarizing film protective film 121 is used as a light absorbing layer, for example, the transmittance at a wavelength of 380nm is preferably 5% or less, more preferably 3% or less, and further preferably 2% or less, and its lower limit is, for example, 0.1% or more and 1% or more. The transmittance at a wavelength of 390nm is preferably 35% or less, more preferably 30% or less, and further preferably 28% or less, and its lower limit is, for example, 10% or more, 20% or more, and 25% or more. The transmittance at a wavelength of 400 nm is preferably 70% or less, more preferably 68% or less, and its lower limit is, for example, 50% or more, 60% or more, or 65% or more. The transmittance at a wavelength of 420 nm is preferably 90% or less, and its lower limit is, for example, 80% or more, or 85% or more. It should be noted that, in addition to the ultraviolet absorber, an infrared absorber such as a phthalocyanine light absorber, a naphthalocyanine light absorber, a polymethine light absorber, a diphenylmethane light absorber, a triphenylmethane light absorber, a quinone light absorber, or an azo light absorber may be mixed.
[0128] As the polarizing film protective film 121, for example, Figure 3 The structure shown in (a) to (c). Figure 3 The polarizing film protective films 121A to 121C shown in (a) to (c) can be used as Figure 1 It should be noted that, for convenience, in these figures, in addition to the polarizing film protective films 121A to 121C, the polarizing film protective films 121A to 121C are also shown. Figure 1 The polarizing film 120 and the polarizing film protective film 122 are shown.
[0129] (A) Polarizing film protective film 121A
[0130] Figure 3The polarizing film protective film 121A shown in (a) includes a polarizing film protective film layer 121A-1 and a coating layer 121A-2. For example, the polarizing film protective film 121A-1 may contain a light absorber, and / or the coating layer 121A-2 may contain a light absorber to form the polarizing film protective film 121A having light absorption capability.
[0131] As materials constituting the polarizing film protective film layer 121A-1, for example, thermoplastic resins with excellent transparency, mechanical strength and thermal stability can be cited. As specific examples of such thermoplastic resins, cellulose resins such as triacetyl cellulose, polyester resins, polyethersulfone resins, polysulfone resins, polycarbonate resins, polyamide resins, polyimide resins, polyolefin resins, (meth) acrylic resins, cyclic polyolefin resins (norbornene resins), polyarylate resins, polystyrene resins, PVA resins, and mixtures thereof can be cited. The polarizing film protective film can also function as a phase difference film.
[0132] The thickness of polarizing film protective film layer 121A-1 can be appropriately adjusted for the purpose of adjusting the moisture content of polarizing film laminate 12. In view of strength, workability such as handling, thin film properties, etc., it is 20 to 60 μm, preferably 30 to 50 μm.
[0133] The polarizing film protective film layer 121A-1 may contain one or more arbitrary additives, such as antioxidants, lubricants, plasticizers, mold release agents, anti-coloring agents, flame retardants, nucleating agents, antistatic agents, pigments, colorants, and the like.
[0134] Examples of the light absorber contained in the polarizing film protective film layer 121A-1 include benzotriazole-based, benzophenone-based, phenyl salicylate-based, and triazine-based ultraviolet absorbers. Examples of the benzotriazole-based ultraviolet absorber include 2-(5-methyl-2-hydroxyphenyl)benzotriazole, 2-(2H-benzotriazole-2-yl)-p-cresol, 2-(2H-benzotriazole-2-yl)-4,6-di-tert-amylphenol, and 2-(2'-hydroxy-5'-methacryloyloxyethylphenyl)-2H-benzotriazole. Examples of the benzophenone-based ultraviolet absorbers include 2-hydroxy-4-octyloxybenzophenone, 2,4-dihydroxybenzophenone, 2-hydroxy-4-methoxy-4'-chlorobenzophenone, 2,2-dihydroxy-4-methoxybenzophenone, and 2,2-dihydroxy-4,4'-dimethoxybenzophenone. Examples of the phenyl salicylate-based ultraviolet absorbers include p-tert-butylphenyl salicylate. As the triazine type ultraviolet absorber, for example, 2,4-diphenyl-6-(2-hydroxy-4-methoxyphenyl)-1,3,5-triazine, 2,4-diphenyl-6-(2-hydroxy-4-ethoxyphenyl)-1,3,5-triazine, 2,4-diphenyl-(2-hydroxy-4-propoxyphenyl)-1,3,5-triazine, 2,4-diphenyl-(2-hydroxy-4-butoxyphenyl)-1,3,5-triazine, 2,4-diphenyl-6-(2-hydroxy-4-butoxyphenyl)-1,3,5 -triazine, 2,4-diphenyl-6-(2-hydroxy-4-hexyloxyphenyl)-1,3,5-triazine, 2,4-diphenyl-6-(2-hydroxy-4-octyloxyphenyl)-1,3,5-triazine, 2,4-diphenyl-6-(2-hydroxy-4-dodecyloxyphenyl)-1,3,5-triazine, 2,4-diphenyl-6-(2-hydroxy-4-benzyloxyphenyl)-1,3,5-triazine, 2,4-diphenyl-6-(2-hydroxy-4-butoxyethoxyphenyl)-1,3,5-triazine, etc. These light absorbers can be contained by mixing them in the polarizing film protective film.
[0135] As a specific example of coating 121A-2, hard coating, anti-glare layer, anti-adhesion layer, anti-reflection layer, conductive layer, etc. can be cited. Among them, the manufacturing method of the present invention is particularly useful in the case of forming a hard coating. As a material constituting the coating, a resin material (monomer, oligomer, prepolymer and / or polymer) is included. In one embodiment, as a resin material, a thermosetting or photocurable curable compound is included. If a material of a coating containing a curable compound is used, a hard coating or an anti-glare layer can be formed. The curable compound can be any compound in a monomer, an oligomer and a prepolymer. As a curable compound, a multifunctional monomer or oligomer can be used, for example, a monomer or oligomer having more than 2 (meth) acryloyl groups, a carbamate (meth) acrylate or an oligomer of a carbamate (meth) acrylate, an epoxy monomer or oligomer, a silicone monomer or oligomer, etc. can be listed.
[0136] In view of thinness, the thickness of the coating layer 121A-2 is 10 μm or less, preferably 8 μm or less, and more preferably 6 μm or less, and its lower limit is, for example, 1 μm or more, 2 μm or more, or 4 μm or more.
[0137] As the light absorber contained in the coating 121A-2, for example, benzotriazole-based, benzophenone-based, phenyl salicylate-based, and triazine-based ultraviolet absorbers can be cited. As the benzotriazole-based ultraviolet absorber, for example, 2-(5-methyl-2-hydroxyphenyl)benzotriazole, 2-(2H-benzotriazole-2-yl)-p-cresol, 2-(2H-benzotriazole-2-yl)-4,6-di-tert-amylphenol, 2-(2'-hydroxy-5'-methacryloyloxyethylphenyl)-2H-benzotriazole, etc. can be cited. As the benzophenone-based ultraviolet absorber, for example, 2-hydroxy-4-octyloxybenzophenone, 2,4-dihydroxybenzophenone, 2-hydroxy-4-methoxy-4'-chlorobenzophenone, 2,2-dihydroxy-4-methoxybenzophenone, 2,2-dihydroxy-4,4'-dimethoxybenzophenone, etc. can be cited. Examples of the phenyl salicylate ultraviolet absorber include p-tert-butylphenyl salicylate. Examples of the triazine ultraviolet absorber include 2,4-diphenyl-6-(2-hydroxy-4-methoxyphenyl)-1,3,5-triazine, 2,4-diphenyl-6-(2-hydroxy-4-ethoxyphenyl)-1,3,5-triazine, 2,4-diphenyl-(2-hydroxy-4-propoxyphenyl)-1,3,5-triazine, 2,4-diphenyl-(2-hydroxy-4-butoxyphenyl)-1,3,5-triazine, and 2,4-diphenyl-6-(2-hydroxy-4-butoxyphenyl)-1,3,5-triazine. 5-triazine, 2,4-diphenyl-6-(2-hydroxy-4-hexyloxyphenyl)-1,3,5-triazine, 2,4-diphenyl-6-(2-hydroxy-4-octyloxyphenyl)-1,3,5-triazine, 2,4-diphenyl-6-(2-hydroxy-4-dodecyloxyphenyl)-1,3,5-triazine, 2,4-diphenyl-6-(2-hydroxy-4-benzyloxyphenyl)-1,3,5-triazine, 2,4-diphenyl-6-(2-hydroxy-4-butoxyethoxyphenyl)-1,3,5-triazine, etc. These light absorbers can be contained by mixing them in the resin forming the coating layer.
[0138] In order to achieve the above-mentioned transmittance, from the perspectives of obtaining sufficient light absorption capacity and thin layer properties, the total thickness of the light absorption layer composed of the polarizing film protective film layer 121A-1 and / or the coating 121A-2, that is, the total thickness of the polarizing film protective film layer 121A-1 with light absorption capacity and / or the coating 121A-2 with light absorption capacity is 25 to 65 μm, preferably 35 to 55 μm or less, and more preferably 40 to 50 μm.
[0139] (B) Polarizing film protective film 121B
[0140] Figure 3The polarizing film protective film 121B shown in (b) includes a plurality of polarizing film protective film layers, here two polarizing film protective film layers 121B-1 and 121B-3, and an adhesive layer 121B-2 for bonding these polarizing film protective film layers 121B-1 and 121B-3 together. The polarizing film protective film 121B having light absorption capability can be formed by, for example, including a light absorber in either or both of the polarizing film protective film layers 121B-1 and 121B-3.
[0141] As the material constituting the polarizing film protection film layers 121B- 1 and 121B- 3 , the same material as that of the optical film protection film layer 121A- 1 can be used.
[0142] The light absorber contained in the polarizing film protection film layers 121B-1 and 121B-3 may be the same light absorber as that contained in the polarizing film protection film layer 121A-1. These light absorbers may be contained in the polarizing film protection film layer 121A-1 in the same manner as that used in the polarizing film protection film layer 121A-1.
[0143] In order to achieve the above-mentioned transmittance, from the perspective of obtaining sufficient light absorption capacity and thin layer properties, the total thickness of the light absorption layer composed of the polarizing film protective film layers 121B-1 and 121B-3, that is, the thickness of the polarizing film protective film layers 121B-1 and 121B-3 with light absorption capacity is 25 to 105 μm, preferably 60 to 100 μm, and more preferably 70 to 90 μm.
[0144] As the adhesive layer 121B- 2 , for example, an ultraviolet curing adhesive or a doping curing adhesive described later can be used.
[0145] (C) Polarizing film protective film 121C
[0146] Figure 3 The polarizing film protective film 121C shown in (c) includes only the polarizing film protective film layer 121C having light absorption capability.
[0147] As a material constituting the polarizing film protection film layer 121C, the same material as that of the optical film protection film layer 121A- 1 can be used.
[0148] As the light absorber contained in the polarizing film protection film layer 121C, the same light absorber as that contained in the polarizing film protection film layer 121A-1 can be used. These light absorbers can be contained in the same manner as that of the polarizing film protection film layer 121A-1.
[0149] In order to obtain sufficient light absorption capacity and thin layer, the thickness of the polarizing film protective film layer 121C, that is, the thickness of the light absorption layer, is 25 to 105 μm, preferably 60 to 100 μm, and more preferably 70 to 90 μm. Figure 3 The plurality of polarizing film protection films 121B-1 and 121B-3 shown in (b) are combined into one polarizing film protection film layer.
[0150] 2-2-3. Others
[0151] The light absorbing layer may be formed by any one of cover plate 14, transparent adhesive 13, etc., and polarizing film protective film 121, or by a combination thereof. When a plurality of layers are combined to form the light absorbing layer, the entire device may be adjusted to a desired transmittance similarly to a general device.
[0152] 2-3. Other optical films
[0153] The polarizing film and the polarizing film protective films 121 and 122 can be directly bonded, but can also be stacked with other optical films. There is no particular limitation on other optical films, and for example, phase difference films, viewing angle compensation films, etc. can be used. The phase difference film as other optical films can be a film having the function of a protective film.
[0154] As described above, the polarizing film protective films 121 and 122 may also have the function of a phase difference film, but in this case, the phase difference film as another optical film may be omitted. On the other hand, in the case where the polarizing film protective film also has the function of a phase difference film, a phase difference film may also be provided as another optical film. In this case, two or more layers of phase difference films are substantially included.
[0155] 2-4. Adhesive
[0156] As Figure 3 The adhesive layer 121B-2 shown in (b), the adhesive used for joining the polarizing film 120 with the polarizing film protective films 121 and 122, or the adhesive used for joining other optical films such as phase difference films with them, can use, for example: free radical polymerization curing type (ultraviolet curing type) adhesive, cationic polymerization curing type adhesive, water-based (doped) adhesive.
[0157] (Free radical polymerization curing adhesive)
[0158] The above-mentioned free radical polymerization curable adhesive contains a free radical polymerizable compound as a curable compound. The free radical polymerizable compound can be a compound that is cured by active energy rays or a compound that is cured by heat. Examples of active energy rays include electron beams, ultraviolet rays, and visible light.
[0159] As the above-mentioned free radical polymerizable compound, for example, a compound having a free radical polymerizable functional group having a carbon-carbon double bond such as a (meth)acryloyl group and a vinyl group can be cited. As the free radical polymerizable compound, a polyfunctional free radical polymerizable compound is preferably used. The free radical polymerizable compound can be used alone or in combination of two or more. In addition, a polyfunctional free radical polymerizable compound and a monofunctional free radical polymerizable compound can also be used in combination.
[0160] As the above-mentioned polymerizable compound, preferably a compound with a high logP value (octanol / water partition coefficient) is used, and as a free radical polymerizable compound, preferably a compound with a high logP value is used. Here, the logP value is an index characterizing the lipophilicity of a substance, and represents the logarithmic value of the partition coefficient of octanol / water. A high logP value means lipophilicity, that is, means that the water absorption rate is low. The logP value can be measured (flask penetration method recorded in JIS-Z-7260), or it can be calculated based on the structure of each compound as a constituent component (curable component, etc.) of the curable adhesive and calculated by calculation (ChemDraw Ultra manufactured by Cambridge Soft).
[0161] The logP value of the radical polymerizable compound is preferably 2 or more, more preferably 3 or more, and particularly preferably 4 or more. Within such a range, deterioration of the polarizer due to moisture can be prevented, and a polarizing film having excellent durability under high temperature and high humidity can be obtained.
[0162] Examples of the polyfunctional radical polymerizable compound include tripropylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, 1,10-decanediol diacrylate, 2-ethyl-2-butylpropylene glycol di(meth)acrylate, bisphenol A di(meth)acrylate, bisphenol A ethylene oxide adduct di(meth)acrylate, bisphenol A propylene oxide adduct di(meth)acrylate, bisphenol A diglycidyl ether di(meth)acrylate, neopentyl glycol di(meth)acrylate, tricyclodecane dimethanol di(meth)acrylate, cyclic trimethylolpropane formal(meth)acrylate, dimethacrylate, and bisphenol A diglycidyl ether di(meth)acrylate. Esterification products of (meth)acrylates and polyols such as alkanediol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, dipentaerythritol hexa(meth)acrylate, and EO-modified diglycerol tetra(meth)acrylate; 9,9-bis[4-(2-(meth)acryloyloxyethoxy)phenyl]fluorene; epoxy (meth)acrylate; urethane (meth)acrylate; polyester (meth)acrylate, etc.
[0163] Among the above-mentioned multifunctional free radical polymerizable compounds, those with high logP values are preferred. Examples of such compounds include alicyclic (meth)acrylates such as tricyclodecane dimethanol di(meth)acrylate (logP=3.05) and isobornyl (meth)acrylate (logP=3.27); long-chain aliphatic (meth)acrylates such as 1,9-nonanediol di(meth)acrylate (logP=3.68) and 1,10-decanediol diacrylate (logP=4.10); polybranched (meth)acrylates such as hydroxypivalic acid neopentyl glycol (meth)acrylate adduct (logP=3.35) and 2-ethyl-2-butylpropylene glycol di(meth)acrylate (logP=3.92); (Meth)acrylates containing aromatic rings, such as bisphenol A di(meth)acrylate (logP=5.46), bisphenol A ethylene oxide 4 mole addition product di(meth)acrylate (logP=5.15), bisphenol A propylene oxide 2 mole addition product di(meth)acrylate (logP=6.10), bisphenol A propylene oxide 4 mole addition product di(meth)acrylate (logP=6.43), 9,9-bis[4-(2-(meth)acryloyloxyethoxy)phenyl]fluorene (logP=7.48), and p-phenylphenol (meth)acrylate (logP=3.98).
[0164] When a multifunctional free radical polymerizable compound and a monofunctional free radical polymerizable compound are used in combination, the content ratio of the multifunctional free radical polymerizable compound is preferably 20 to 97% by weight, more preferably 50 to 95% by weight, further preferably 75 to 92% by weight, and particularly preferably 80 to 92% by weight relative to the total amount of the free radical polymerizable compound. If it is within such a range, a polarizing film having excellent durability under high temperature and high humidity can be obtained.
[0165] Examples of the monofunctional radical polymerizable compound include (meth)acrylamide derivatives having a (meth)acrylamide group. When a (meth)acrylamide derivative is used, a pressure-sensitive adhesive layer having excellent adhesiveness can be formed with high productivity. Specific examples of (meth)acrylamide derivatives include N-alkyl (meth)acrylamide derivatives such as N-methyl (meth)acrylamide, N,N-dimethyl (meth)acrylamide, N,N-diethyl (meth)acrylamide, N-isopropyl (meth)acrylamide, N-butyl (meth)acrylamide, and N-hexyl (meth)acrylamide; N-hydroxyalkyl (meth)acrylamide derivatives such as N-hydroxymethyl (meth)acrylamide, N-hydroxyethyl (meth)acrylamide, and N-hydroxymethyl-N-propane (meth)acrylamide; N-aminoalkyl (meth)acrylamide derivatives such as aminomethyl (meth)acrylamide and aminoethyl (meth)acrylamide; N-alkoxy (meth)acrylamide derivatives such as N-methoxymethylacrylamide and N-ethoxymethylacrylamide; N-mercaptoalkyl (meth)acrylamide derivatives such as mercaptomethyl (meth)acrylamide and mercaptoethyl (meth)acrylamide, and the like. In addition, as heterocyclic (meth)acrylamide derivatives in which the nitrogen atom of the (meth)acrylamide group forms a heterocyclic ring, for example, N-acryloylmorpholine, N-acryloylpiperidine, N-methacryloylpiperidine, N-acryloylpyrrolidine, etc. can be used. Among these, N-hydroxyalkyl (meth)acrylamide derivatives are preferred, and N-hydroxyethyl (meth)acrylamide is more preferred.
[0166] In addition, as the above-mentioned monofunctional free radical polymerizable compound, a (meth)acrylic acid derivative having a (meth)acryloyloxy group can be used; carboxyl group-containing monomers such as (meth)acrylic acid, carboxyethyl acrylate, carboxypentyl acrylate, itaconic acid, maleic acid, fumaric acid, crotonic acid, and isocrotonic acid; lactam vinyl monomers such as N-vinylpyrrolidone, N-vinyl-ε-caprolactam, and methylvinylpyrrolidone; vinylpyridine, vinylpiperidone, vinylpyrimidine, vinylpiperazine, vinylpyrazine, vinylpyrrole, vinylimidazole, and vinyl Vinyl monomers having a nitrogen-containing heterocyclic ring such as oxazole and vinyl morpholine, etc.
[0167] When a multifunctional free radical polymerizable compound and a monofunctional free radical polymerizable compound are used in combination, the monofunctional free radical polymerizable compound is preferably contained in an amount of 3 to 80% by weight, more preferably 5 to 50% by weight, further preferably 8 to 25% by weight, and particularly preferably 8 to 20% by weight relative to the total amount of the free radical polymerizable compound. If it is within such a range, a polarizing film having excellent durability under high temperature and high humidity can be obtained.
[0168] The above-mentioned free radical polymerization curing adhesive may further contain other additives. In the case where the free radical polymerization curing adhesive contains a curable compound cured by active energy rays, the adhesive may further contain, for example, a photopolymerization initiator, a photoacid generator, a silane coupling agent, etc. In addition, in the case where the free radical polymerization curing adhesive contains a curable compound cured by heat, the adhesive may further contain a thermal polymerization initiator, a silane coupling agent, etc. In addition, as other additives, for example, an inhibitor, a polymerization initiation aid, a leveling agent, a wettability improver, a surfactant, a plasticizer, an ultraviolet absorber, an inorganic filler, a pigment, a dye, etc. can be cited.
[0169] (Cationic polymerization curing adhesive)
[0170] The above-mentioned cationic polymerization curing adhesive contains a cationic polymerizable compound as a curable compound. As the cationic polymerizable compound, for example, a compound having an epoxy group and / or an oxetane group can be cited. The compound having an epoxy group is preferably a compound having at least two epoxy groups in the molecule. As the compound having an epoxy group, for example, a compound having at least two epoxy groups and at least one aromatic ring (aromatic epoxy compounds), a compound having at least two epoxy groups in the molecule and at least one of which is formed between two adjacent carbon atoms constituting an alicyclic ring (alicyclic epoxy compounds), etc. can be cited.
[0171] Preferably, the above-mentioned cationic polymerization curing adhesive contains a photocationic polymerization initiator. The photocationic polymerization initiator generates cationic species or Lewis acid by irradiation with active energy rays such as visible light, ultraviolet rays, X-rays, electron beams, etc., thereby initiating the polymerization reaction of epoxy groups and oxetane groups. In addition, the cationic polymerization curing adhesive may further contain the above-mentioned additives.
[0172] (Water-based adhesive)
[0173] As the aqueous adhesive, for example, aqueous solutions (for example, having a solid content concentration of 0.5 to 60% by weight) of aqueous adhesives such as isocyanate adhesives, PVA adhesives, gelatin adhesives, vinyl latex adhesives, and aqueous polyester adhesives can be preferably used.
[0174] The adhesive may be applied to any one of the polarizing film 120, the polarizing film protective films 121, 122, and other optical films, or to any two of them. Generally, it is preferred to immerse the polarizing film in an aqueous adhesive solution and then laminate it with the polarizing film protective films 121, 122 by a roll laminator or the like. The thickness of the adhesive layer is not particularly limited, and is, for example, about 30 nm to 1000 nm in thickness after drying.
[0175] After laminating the polarizing film, the polarizing film protective film, and other optical films with an adhesive, the laminate is subjected to a drying process. In the drying process of the laminate, in addition to the purpose of drying and solidifying the adhesive, it is also carried out for the purpose of reducing the moisture content of the polarizing film laminate to improve the initial optical properties. As a drying method, heating drying is generally used. As drying conditions, the range of 50 to 95°C is preferred, and the range of 60 to 85°C is more preferred.
[0176] The drying conditions of the laminate are not particularly limited, but in consideration of treatment efficiency and practicality, the drying temperature is preferably 50° C. or higher, and in view of making the optical properties of the polarizing film laminate uniform, it is preferably 95° C. or lower. The drying temperature may be increased stepwise within the above temperature range.
[0177] The drying of the laminate can be carried out continuously with the bonding process of the polarizing film, the polarizing film protective film, and other optical films. In addition, after the laminate of the polarizing film, the polarizing film protective film, and other optical films is temporarily wound into a roll state, it can be dried as another treatment.
[0178] Generally speaking, in order to reduce the moisture content of the polarizing film laminate, high temperature / long time drying conditions are necessary. From the perspective of reducing the moisture content of the polarizing film laminate, high temperature / long time drying is preferred, but on the other hand, it sometimes causes a reduction in the optical properties of the polarizing film laminate. By using a polarizing film protective film with a small saturated water absorption and a polarizing film protective film with a high moisture permeability, the moisture content of the polarizing film laminate can be adjusted to the above-mentioned desired range even without using strict drying conditions.
[0179] 2-5. Adhesive
[0180] The adhesive described in the above-mentioned "1-3. Transparent adhesive" can be used in the same manner.
[0181] 3. Reliability evaluation project
[0182] Multiple phenomena that may occur in polarizing film laminates, namely, polyeneization, discoloration, and reddening by heating, were evaluated. The mechanism of each phenomenon is not yet clear, but it can be roughly estimated as follows.
[0183] <Polyene>
[0184] In a high temperature and high humidity environment, the transmittance of the polarizing film laminate decreases. In addition, the transmittance of the polarizing film laminate decreases when exposed to light in the ultraviolet and visible light regions. It is speculated that this decrease is due to the polyeneization of PVA. Polyene refers to -(CH=CH) n-, which can be formed in the polarizing film by heating and light energy. Polyene will cause the transmittance of the polarizing film to be significantly reduced. In addition, in a high temperature and high humidity environment, in an ultraviolet region and in a light irradiation environment in the visible light region, the PVA-polyiodine complex is destroyed and I - and I 2 .
[0185] The polyeneization of PVA is considered to be as shown in the following chemical formula 1. Due to the iodine (I 2 ) and heating and light energy promote the dehydration reaction.
[0186] (Chemical formula 1)
[0187]
[0188] It can be considered that the PVA-polyiodine complex in the polarizing film is destroyed by heating and light energy, and the I 2 and OH groups in PVA to form a charge transfer complex (HO···I 2 ), followed by polyeneization via the OI group.
[0189] <Decolorization>
[0190] In the iodine-dyed and stretched PVA film (polarizing film), iodine is I 3 - and I 5 - The polyiodide ions of PVA form a complex (PVA polyiodide complex) with the oriented PVA. At this time, PVA forms crosslinking points through a crosslinking agent such as boric acid, thereby maintaining the orientation.
[0191] However, if the polarizing film is placed in a light irradiation environment under high temperature and high humidity, in the ultraviolet region, or in the visible light region, the hydrolysis of the boric acid crosslinking will be induced, resulting in a decrease in the orientation of the PVA and the disintegration of the PVA polyiodine complex. As a result, the visible light absorption based on the PVA polyiodine complex decreases, and the transmittance on the long wavelength side of about 700nm and the short wavelength side of about 410nm increases. In this way, discoloration in black display will occur in the polarizing film placed in a light irradiation environment under high temperature and high humidity, in the ultraviolet region, or in the visible light region.
[0192] <Heating and turning red>
[0193] In the iodine-dyed and stretched PVA film (polarizing film), iodine is I 3 - and I 5 -The polyiodide ion forms a complex with PVA (PVA polyiodide complex). 3 - It has a broad absorption peak around 470nm. 5 - It has a broad absorption peak around 600nm. 3 - The complex is responsible for the absorption on the short wavelength side (blue side), PVA-I 5 - The complex is responsible for absorption on the long wavelength side (red side).
[0194] However, the PVA-I 5 - The complex has weak resistance to heating and light energy. If the polarizing film is placed in an environment with high temperature, ultraviolet light, or visible light, the PVA and I 5 - The complex formation of I 5 - break down.
[0195] Therefore, in the polarizing film placed in an environment of light irradiation in the ultraviolet region or the visible light region at high temperature, the PVA-I responsible for the absorption on the long wavelength side 5 - As the amount of complexes decreases, the transmittance on the long wavelength side of about 700 nm increases, and the color of the polarizing film changes to red.
[0196] 4. Examples and Comparative Examples
[0197] Hereinafter, although an Example and a comparative example are demonstrated together, it is needless to say that this invention is not limited to the description in these Examples.
[0198] As examples and comparative examples, the “thickness of polarizing film (μm)”, and / or the “iodine concentration of polarizing film (wt.%)”, and / or the “water content of polarizing film laminate (g / m 2 )”, samples of various polarizing film stacks with different “transmittances” for light of short wavelengths (such as 380 μm).
[0199] <Film thickness of polarizing film>
[0200] The film thickness (μm) of the polarizing film is measured using a spectroscopic film thickness meter MCPD-1000 (manufactured by Otsuka Electronics Co., Ltd.). The thickness of the polarizing film protective film is also measured using the spectroscopic film thickness meter. The polarizing film contained in the sample can be taken out by immersing the sample in a solvent and dissolving the polarizing film protective film. As the solvent, respectively, for example, when the polarizing film protective film is a cellulose triacetate resin, dichloromethane is used, when the polarizing film protective film is a cycloolefin resin, cyclohexane is used, and when the polarizing film protective film is an acrylic resin, methyl ethyl ketone is used. It should be noted that when the resin of the polarizing film protective film provided on one side of the polarizing film is different from the resin of the polarizing film protective film provided on the other side, the above-mentioned solvent is used to dissolve each resin in turn.
[0201] <Iodine concentration of polarizing film>
[0202] When producing a polarizing film, the iodine concentration (wt. %) of the polarizing film can be changed by adjusting, for example, the concentration of the iodine aqueous solution in which the PVA-based film or the PVA layer is immersed and the immersion time.
[0203] The iodine concentration of the polarizing film is measured by the following method: The polarizing film contained in the sample can be taken out by immersing the sample in a solvent and dissolving the polarizing film protective film in the same manner as when measuring the film thickness of the polarizing film.
[0204] (Fluorescence X-ray measurement)
[0205] When measuring the iodine concentration of the polarizing film, first, the iodine concentration was quantitatively determined using a calibration curve method of fluorescent X-ray analysis. A fluorescent X-ray analyzer ZSX-PRIMUS IV (manufactured by Rigaku Corporation) was used as an apparatus.
[0206] The value directly obtained by the fluorescent X-ray analyzer is not the concentration of each element, but the fluorescent X-ray intensity (kcps) of the wavelength inherent to each element. Therefore, in order to determine the iodine concentration contained in the polarizing film, it is necessary to use a calibration curve to convert the fluorescent X-ray intensity into a concentration. The iodine concentration of the polarizing film in this specification refers to the iodine concentration (wt%) based on the weight of the polarizing film.
[0207] (Preparation of calibration curve)
[0208] The calibration curve was prepared according to the following steps.
[0209] 1. A known amount of potassium iodide was dissolved in a PVA aqueous solution to prepare 7 types of PVA aqueous solutions containing iodine at known concentrations. The PVA aqueous solution was applied to polyethylene terephthalate, dried, and then peeled off to prepare samples 1 to 7 of PVA films containing iodine at known concentrations.
[0210] The iodine concentration (wt %) of the PVA film was calculated according to the following mathematical formula 1.
[0211] [Mathematical formula 1]
[0212] Iodine concentration (wt%) = {potassium iodide amount (g) / (potassium iodide amount (g) + PVA amount (g))} × (127 / 166)
[0213] (Molecular weight of iodine: 127Molecular weight of potassium: 39)
[0214] 2. For the produced PVA film, the fluorescence X-ray intensity (kcps) corresponding to iodine was measured using a fluorescence X-ray analyzer ZSX-PRIMUS IV (manufactured by Rigaku Corporation). The fluorescence X-ray intensity (kcps) was set as the peak value of the fluorescence X-ray spectrum. In addition, the film thickness of the produced PVA film was measured using a spectroscopic film thickness meter MCPD-1000 (manufactured by Otsuka Electronics Co., Ltd.).
[0215] 3. The fluorescence X-ray intensity was divided by the thickness (μm) of the PVA film to obtain the fluorescence X-ray intensity per unit thickness of the film (kcps / μm). Table 1 shows the iodine concentration and the fluorescence X-ray intensity per unit thickness of each sample.
[0216] [Table 1]
[0217]
[0218] 4. Based on the results shown in Table 1, a calibration curve was prepared with the fluorescence X-ray intensity per unit thickness of the PVA film (kcps / μm) as the horizontal axis and the iodine concentration (wt%) contained in the PVA film as the vertical axis. The prepared calibration curve is shown in Figure 4 The mathematical formula for calculating the iodine concentration from the fluorescent X-ray intensity per unit thickness of the PVA film using the calibration curve is determined as shown in Mathematical Formula 2. It should be noted that, Figure 4 The R2 in is the correlation coefficient.
[0219] [Mathematical formula 2]
[0220] (iodine concentration) (wt%) = 14.474 × (fluorescent X-ray intensity per unit thickness of PVA film) (kcps / μm)
[0221] (Calculation of iodine concentration)
[0222] The fluorescent X-ray intensity per unit thickness (kcps / μm) was calculated by dividing the fluorescent X-ray intensity obtained by measuring the sample by the thickness. The fluorescent X-ray intensity per unit thickness of each sample was substituted into Formula 2 to calculate the iodine concentration.
[0223] <Water content of polarizing film laminate>
[0224] Moisture content of polarizing film laminate (g / m 2 ) can be mainly determined by adjusting the film thickness of the polarizing film, the material and thickness of the polarizing film protective film bonded to the polarizing film, etc. In addition, it can also be adjusted by cross-linking treatment (boric acid content, etc.) during the manufacture of the polarizing film.
[0225] The moisture content of the polarizing film laminate is measured by the following method.
[0226] First, the polarizing film laminated bodies obtained in Examples and Comparative Examples were cut into a square of 0.1 m×0.1 m.
[0227] Put the cut samples into a thermostat and humidity chamber and place them in an environment with a temperature of 23°C and a relative humidity of 55% for 48 hours. Then, take out the samples in a clean room with the same environment as that in the thermostat, i.e., a temperature of 23°C and a relative humidity of 55%, and measure the weight within 5 minutes after taking them out. The sample weight at this time is set as the initial weight W1 (g). It should be noted that as long as it is within about 15 minutes after taking it out, even if the temperature in the clean room fluctuates by about 2°C to 3°C, and even if the relative humidity in the clean room fluctuates by about ±10%, it will not have a substantial impact on the initial weight.
[0228] Next, the sample is put into a dryer and dried at 120°C for 2 hours. Then, the dried sample is taken out in the clean room set at a temperature of 23°C and a relative humidity of about 55%, and the weight is measured within 10 minutes after taking it out. The sample weight at this time is set as the dried weight W2 (g). Different from the above, it is set to within 10 minutes instead of within 5 minutes, taking into account the cooling time. It should be noted that, as mentioned above, as long as it is within about 15 minutes after taking it out, it will not have a substantial impact on the dried weight.
[0229] The equilibrium moisture content M (g / m2) of the polarizing film laminate is calculated from the initial weight W1 and the weight W2 of the sample after drying by the following formula: 2 ).
[0230] (Formula) M = (W1-W2) / (0.1×0.1)
[0231] The “water content of the polarizing film laminate” referred to in the present invention refers to the equilibrium water content calculated by the above-mentioned method.
[0232] <Light absorption ability>
[0233] In order to evaluate the effect of suppressing the influence of short-wavelength light, the transmittance of the polarizing film protective film located closer to the visible side than the polarizing film was measured at wavelengths of 380 μm, 390 μm, 400 μm, and 420 μm according to the JIS-Z-8701 color representation method. U-4100 manufactured by Hitachi, Ltd. was used for the measurement.
[0234] [Example 1]
[0235] (Production of polarizing film)
[0236] As the resin substrate, a long amorphous isophthalic acid copolymer polyethylene terephthalate film (isophthalic acid group modification rate 5 mol%, thickness: 100 μm) (modification rate = isophthalic acid unit / (ethylene terephthalate unit + isophthalic acid unit)) was used. One side of the resin substrate was subjected to corona treatment (treatment conditions: 55 W·min / m 2 ), and an aqueous solution containing PVA (polymerization degree 4200, saponification degree 99.2 mol%) and 13 parts by weight of potassium iodide relative to PVA was applied to the corona treated surface at room temperature. The PVA was prepared by mixing 90 parts by weight of PVA (polymerization degree 4200, saponification degree 99.2 mol%) and 10 parts by weight of acetoacetyl-modified PVA (manufactured by Nippon Synthetic Chemical Industry Co., Ltd., trade name "GOHSEFIMER Z410"), and then dried at 60°C to form a PVA-based resin layer with a thickness of 13 μm, thereby producing a laminate.
[0237] The obtained laminate was subjected to free-end uniaxial stretching to 2.4 times in the longitudinal direction (length direction) between rolls having different peripheral speeds in an oven at 130° C. (auxiliary stretching in a gas atmosphere).
[0238] Next, the laminate was immersed in an insolubilization bath (boric acid aqueous solution prepared by mixing 4 parts by weight of boric acid with 100 parts by weight of water) at a liquid temperature of 40° C. for 30 seconds (insolubilization treatment).
[0239] Next, the film was immersed in a dyeing bath (an iodine aqueous solution prepared by mixing iodine and potassium iodide at a weight ratio of 1:7 per 100 parts by weight of water) at a liquid temperature of 30° C. for 60 seconds while adjusting the concentration so as to give a predetermined transmittance (dyeing treatment).
[0240] Next, the mixture was immersed in a crosslinking bath (boric acid aqueous solution prepared by blending 3 parts by weight of potassium iodide and 5 parts by weight of boric acid with respect to 100 parts by weight of water) at a liquid temperature of 40° C. for 30 seconds (crosslinking treatment).
[0241] Then, while the laminate was immersed in a boric acid aqueous solution (boric acid concentration: 3.0 wt%) at a liquid temperature of 70°C, it was uniaxially stretched (stretched in aqueous solution) in the longitudinal direction (length direction) between rollers with different peripheral speeds so that the total stretching ratio became 5.5 times.
[0242] Then, the laminated body was immersed in a cleaning bath (an aqueous solution containing 4 parts by weight of potassium iodide per 100 parts by weight of water) at a liquid temperature of 20° C. (cleaning treatment).
[0243] Thereafter, the sample was dried in an oven maintained at 90° C. (drying treatment), and was brought into contact with a SUS metal roll maintained at a surface temperature of 75° C. for 2 seconds or more (hot roll drying treatment).
[0244] In this way, a polarizing film having a thickness of 5.4 μm was obtained on the resin substrate.
[0245] (Production of Polarizing Film Laminate)
[0246] A polarizing film protective film is not provided on the side of the obtained polarizing film opposite to the resin substrate (one side of the polarizing film, in other words, the side of the polarizing film opposite to the visible side). On the other hand, the following polarizing film protective film as a polarizing film protective film with light absorption ability is bonded to the side after the resin substrate is peeled off (the other side of the polarizing film, in other words, the visible side of the polarizing film) by using an ultraviolet curing adhesive described later. The polarizing film protective film is formed by a cellulose triacetate film containing a light absorber (manufactured by Konica Minolta, trade name "KC4UY", thickness 40μm), and a hard coating layer (thickness 5μm) containing a light absorber disposed on its visible side. Specifically, the curing adhesive is applied in a manner that the total thickness reaches 1.0μm, and a roller machine is used for bonding. Then, UV light is irradiated from the other side to cure the adhesive, and a polarizing film laminate comprising a polarizing film and a polarizing film protective film with light absorption ability disposed on the other side of the polarizing film is obtained.
[0247] The above-mentioned triacetylcellulose film contains a predetermined amount of light absorber (ultraviolet absorber). On the other hand, Tinosorb S (manufactured by BASF) as a light absorber is contained in the hard coat layer so that the triacetylcellulose film and the hard coat layer as a whole have the transmittance recorded in the absorption capacity of Tables 2 and 3 described later.
[0248] The details of the UV-curable adhesive are as follows. An adhesive was prepared by mixing 40 parts by weight of N-hydroxyethyl acrylamide (HEAA), 60 parts by weight of acryloyl morpholine (ACMO) and 3 parts by weight of a photoinitiator "IRGACURE 819" (manufactured by BASF). The adhesive was applied on a polarizing film so that the thickness of the cured adhesive layer reached 1.0 μm, and ultraviolet rays were irradiated as active energy rays to cure the adhesive. For ultraviolet irradiation, a metal halide lamp enclosed in gallium was used, an irradiation device: Light HAMMER10 manufactured by Fusion UV Systems, Inc., valve: V valve, peak illuminance: 1600 mW / cm 2 , cumulative irradiation 1000 / mJ / cm 2 (wavelength 380 to 440 nm), and the illuminance of ultraviolet rays was measured using the Sola-Check system manufactured by Solatell.
[0249] (Determination of iodine concentration)
[0250] The polarizing film was taken out from the polarizing film laminate using cyclohexane as a solvent, and the iodine concentration of the polarizing film was measured.
[0251] (Measurement of transmittance)
[0252] The polarizing film protective film disposed on the visible side of the polarizing film, that is, the polarizing film protective film composed of the triacetyl cellulose film and the hard coat layer was peeled off from the polarizing film laminate, and the transmittance of the polarizing film protective film was measured.
[0253] [Example 2]
[0254] When the polarizing film of Example 1 was produced, the concentration of the iodine aqueous solution and the immersion time were adjusted in the dyeing process to change the iodine concentration.
[0255] In addition, when the polarizing film laminate of Example 1 was prepared, a cycloolefin film (ZEONOR FILM, 13 μm, manufactured by ZEON Co., Ltd., Japan) was bonded to one side of the polarizing film as a polarizing film protective film using an ultraviolet curing adhesive. Since the cycloolefin film is provided on one side of the polarizing film, it does not affect the value of the light absorption capacity. On the other hand, the other side of the polarizing film was set to the same structure as the other side of Example 1. In addition, the moisture content of the polarizing film laminate was changed.
[0256] The rest is the same as in the first embodiment.
[0257] [Comparative Example 1]
[0258] When the polarizing film laminate of Example 1 was prepared, one side of the polarizing film was set to the same structure as the above-mentioned side of Example 1, and on the other hand, a transparent protective film (manufactured by Nitto Denko Corporation) with a thickness of 20 μm formed of a modified acrylic polymer having a lactone ring structure was bonded to the other side of the polarizing film using an ultraviolet curing adhesive in the same manner as in Example 1 so that the total thickness of the curing adhesive was 1.0 μm. In addition, the water content of the polarizing film laminate was changed.
[0259] The rest is the same as in the first embodiment.
[0260] [Comparative Example 2]
[0261] When the polarizing film laminate of Example 2 was prepared, one side of the polarizing film was set to the same structure as the above-mentioned side of Example 2, and on the other hand, a cycloolefin film (ZEONOR FILM, 25 μm, manufactured by ZEON Co., Ltd., Japan) was bonded to the other side of the polarizing film using an ultraviolet curing adhesive in the same manner as in Example 1 so that the total thickness of the curing adhesive reached 1.0 μm. In addition, the moisture content of the polarizing film laminate was changed.
[0262] The rest is the same as in the second embodiment.
[0263] [Comparative Example 3]
[0264] When the polarizing film of Example 1 was produced, the concentration of the iodine aqueous solution and the immersion time were adjusted during the dyeing process to change the iodine concentration.
[0265] In addition, when the polarizing film laminate of Example 1 was prepared, a cycloolefin film (ZEONOR FILM, 17 μm, manufactured by ZEON Co., Ltd., Japan) was bonded as a polarizing film protective film on one side of the polarizing film using an ultraviolet curing adhesive in the same manner as in Example 1 so that the total thickness of the curing adhesive reached 1.0 μm. On the other hand, the other side of the polarizing film was set to the same structure as the other side of Example 1. In addition, the moisture content of the polarizing film laminate was changed.
[0266] The rest is the same as in the first embodiment.
[0267] [Comparative Example 4]
[0268] When the polarizing film laminate of Comparative Example 3 was prepared, one side of the polarizing film was set to the same configuration as the one side of Comparative Example 3. On the other hand, no polarizing film protective film was provided on the other side of the polarizing film. In addition, the water content of the polarizing film laminate was changed.
[0269] The rest is the same as in Comparative Example 3.
[0270] [Example 3]
[0271] (Production of polarizing film)
[0272] A PVA film with an average degree of polymerization of 2700 and a thickness of 30 μm was stretched and transported while being dyed between rollers with different peripheral speed ratios. First, the PVA film was immersed in a 30°C water bath for 1 minute to swell the film, and then stretched 1.2 times in the transport direction. Then, it was immersed in an aqueous solution (liquid temperature 30°C) of potassium iodide (0.03 wt%) and iodine (0.3 wt%) for 1 minute, thereby being stretched to 3 times in the transport direction while being dyed (based on the unstretched film). Next, the stretched film was immersed in an aqueous solution (bath) of boric acid (4 wt%) and potassium iodide (5 wt%) for 30 seconds, while being stretched to 6 times in the transport direction (based on the unstretched film). After stretching, it was dried in an oven at 40°C for 3 minutes to obtain a 12.0 μm polarizing film.
[0273] (Production of Polarizing Film Laminate)
[0274] As an adhesive, a doping curing adhesive was used. More specifically, an aqueous solution containing a polyvinyl alcohol resin containing an acetoacetyl group (average degree of polymerization 1200, saponification degree 98.5 mol%, acetoacetylation degree 5 mol%) and methylol melamine in a weight ratio of 3:1 was used. Using this adhesive, a transparent protective film (manufactured by Nitto Denko Corporation) with a thickness of 20 μm formed by a modified acrylic polymer having a lactone ring structure was bonded to one side of the polarizing film at a temperature of 30°C. Specifically, the doping curing adhesive was applied in such a manner that the total thickness reached 1.0 μm, and bonding was performed using a roller machine. On the other hand, the polarizing film protective film used in Example 1, i.e., a polarizing film protective film formed by a triacetyl cellulose film containing a light absorber and a hard coating layer containing a light absorber disposed on its visible side, was bonded to the other side of the polarizing film as a polarizing film protective film having light absorption ability by using a doping curing adhesive instead of an ultraviolet curing adhesive in the same manner as on one side. Then, the film was dried by heating at 70° C. for 5 minutes in an oven to obtain a polarizing film laminate having a polarizing film, a polarizing film protective film having no light absorption capability arranged on one side of the polarizing film, and a polarizing film protective film having light absorption capability arranged on the other side.
[0275] (Determination of iodine concentration)
[0276] The polarizing film was taken out from the polarizing film laminate using dichloromethane and methyl ethyl ketone as a solvent, and the iodine concentration of the polarizing film was measured.
[0277] (Measurement of transmittance)
[0278] By the same method as in Example 1, the transmittance was measured.
[0279] [Comparative Example 5]
[0280] When preparing the polarizing film laminate of Example 3, the above-mentioned one side is set to the same structure as that of Example 3, and a polarizing film protective film formed by a cellulose triacetate film containing a light absorber (manufactured by Konica Minolta, trade name "KC2UA", thickness 25μm) and a hard coating layer without light absorption ability arranged on its visible side (manufactured by Nitto Denko Corporation, thickness 9μm) is bonded to the above-mentioned other side as a polarizing film protective film with light absorption ability by doping a curing adhesive in the same method as in Example 3 so that the total thickness of the curing adhesive reaches 1.0μm. In addition, the moisture content of the polarizing film laminate is changed. The hard coating layer is formed by the following method. First, a hard coating forming material is prepared. The material is prepared as follows: a UV curable resin monomer or oligomer containing urethane acrylate as the main component is dissolved in butyl acetate, and to the obtained resin solution (DIC Corporation, trade name "UNIDIC 17-806". Solid content concentration 80% by weight), 5 parts by weight of a photopolymerization initiator (BASF Corporation, product name "IRGACURE906") and 0.01 parts by weight of a leveling agent (DIC Corporation, product name "GRANDIC PC4100") are added per 100 parts by weight of the solid content in the solution, and cyclopentanone (hereinafter referred to as "CPN") and propylene glycol monomethyl ether (hereinafter referred to as "PGM") are added to the above-mentioned mixed solution at a ratio of 45:55 so that the solid content concentration in the above-mentioned solution reaches 36% by weight, thereby preparing a hard coating forming material. The hard coating forming material prepared in this way is applied on a transparent protective film so that the thickness of the hard coating after curing reaches 9 μm, thereby forming a coating film. Next, the samples were dried at 90°C for 1 minute and then irradiated with a high pressure mercury lamp at a cumulative light intensity of 300 mJ / cm 2 The coating film was cured by ultraviolet rays.
[0281] The rest is the same as in the third embodiment.
[0282] [Example 4]
[0283] (Production of polarizing film)
[0284] A PVA film with an average degree of polymerization of 2700 and a thickness of 45 μm was stretched and transported while being dyed between rollers with different peripheral speed ratios. First, the PVA film was immersed in a 30°C water bath for 1 minute to swell the film, and then stretched 1.2 times in the transport direction. Then, it was immersed in an aqueous solution (liquid temperature 30°C) of potassium iodide (0.03 wt%) and iodine (0.3 wt%) for 1 minute, thereby being stretched to 3 times in the transport direction while being dyed (based on the unstretched film). Next, the stretched film was immersed in an aqueous solution (bath) of boric acid (4 wt%) and potassium iodide (5 wt%) for 30 seconds, while being stretched to 6 times in the transport direction (based on the unstretched film). After stretching, it was dried in an oven at 40°C for 3 minutes to obtain a 18.0 μm polarizing film.
[0285] (Production of Polarizing Film Laminate)
[0286] A transparent protective film (manufactured by Nitto Denko Corporation) with a thickness of 30 μm and formed of a modified acrylic polymer having a lactone ring structure was bonded to one side of the polarizing film via a doping curable adhesive in the same manner as in Example 3. On the other hand, the other side of the polarizing film was made into the same structure as that of the other side in Example 3.
[0287] The rest is the same as in the third embodiment.
[0288] [Example 5]
[0289] When preparing the polarizing film laminate of Example 4, the above-mentioned one side is set to the same structure as that of Example 4, and the following polarizing film protective film is joined to the above-mentioned other side by doping with a curable adhesive in the same method as in Example 3 so that the total thickness of the curable adhesive reaches 1.0 μm, wherein the polarizing film protective film is formed by a triacetate cellulose film containing a light absorber (manufactured by Fujifilm Co., Ltd., trade name "TJ40ULF", thickness 40 μm), a triacetate cellulose film containing a light absorber arranged on its visible side (manufactured by Konica Minolta, trade name "KC4UY", thickness 40 μm), and a hard coating layer without light absorption ability arranged on its visible side (manufactured by Nitto Denko Corporation, thickness 9 μm). A triacetyl cellulose film (manufactured by Fujifilm Corporation, trade name "TJ40ULF", thickness 40 μm) and a triacetyl cellulose film (manufactured by Konica Minolta, trade name "KC4UY", thickness 40 μm) were joined via an ultraviolet curing adhesive in a manner that the total thickness of the curing adhesive reached 1.0 μm.
[0290] (Determination of iodine concentration)
[0291] The polarizing film was taken out from the polarizing film laminate using dichloromethane and methyl ethyl ketone as a solvent, and the iodine concentration of the polarizing film was measured.
[0292] (Measurement of transmittance)
[0293] The polarizing film protective film located on the visible side of the polarizing film, namely, the polarizing film protective film composed of the cellulose triacetate film, another cellulose triacetate film, and the hard coat layer was peeled off from the polarizing film laminate, and the transmittance of the polarizing film protective film was measured.
[0294] [Comparative Example 6]
[0295] When preparing the polarizing film laminate of Example 4, a transparent protective film (manufactured by Nitto Denko Corporation) with a thickness of 30 μm formed of a modified acrylic polymer having a lactone ring structure was bonded to one side of the polarizing film via a doped curable adhesive in the same manner as in Example 3. On the other hand, the following polarizing film protective film was bonded to the other side of the polarizing film as a polarizing film protective film with light absorption ability via a doped curable adhesive in the same manner as in Example 3 so that the total thickness of the curable adhesive reached 1.0 μm. The polarizing film protective film was formed with a hard coating layer (manufactured by Nitto Denko Corporation, thickness 9 μm) without light absorption ability on a triacetyl cellulose film (manufactured by Fujifilm Corporation, trade name "TJ40ULF", thickness 40 μm) containing a light absorber. In addition, the moisture content of the polarizing film laminate was changed.
[0296] The rest is the same as in the fourth embodiment.
[0297] [Comparative Example 7]
[0298] When the polarizing film laminate of Comparative Example 6 was prepared, the concentration of the iodine aqueous solution and the immersion time were adjusted in the dyeing process to change the iodine concentration. In addition, the water content of the polarizing film laminate was changed.
[0299] The rest is the same as in Comparative Example 6.
[0300] [Comparative Example 8]
[0301] When the polarizing film laminate of Example 4 was produced, the concentration of the iodine aqueous solution and the immersion time were adjusted in the dyeing process to change the iodine concentration. In addition, the water content of the polarizing film laminate was changed.
[0302] The rest is the same as in the fourth embodiment.
[0303] [Example 6]
[0304] When the polarizing film laminate of Example 4 was produced, the concentration of the iodine aqueous solution and the immersion time were adjusted in the dyeing process to change the iodine concentration. In addition, the water content of the polarizing film laminate was changed.
[0305] The rest is the same as in the fourth embodiment.
[0306] [Example 7]
[0307] (Production of polarizing film)
[0308] When preparing the polarizing film of Example 3, a PVA film having a thickness of 75 μm was stretched and conveyed during the stretching process to obtain a polarizing film having a thickness of 28 μm. In addition, during the dyeing process, the concentration of the iodine aqueous solution and the immersion time were adjusted to change the iodine concentration.
[0309] (Production of Polarizing Film Laminate)
[0310] One side and the other side of the polarizing film had the same configurations as those of the polarizing film of Example 4. In addition, the water content of the polarizing film laminate was changed.
[0311] The rest is the same as in the fourth embodiment.
[0312] [Example 8]
[0313] The moisture content of the polarizing film laminate was changed when preparing the polarizing film laminate of Example 7. In Example 7, the laminate was stretched to 6 times in the transport direction (unstretched film basis) as in Example 4 and then immersed in an aqueous solution (bath) of zinc sulfate (3.5 wt%).
[0314] The other conditions are the same as those in Example 7.
[0315] [Comparative Example 9]
[0316] (Production of polarizing film)
[0317] The polarizing film of Example 7 was used.
[0318] (Production of Polarizing Film Laminate)
[0319] One side of the polarizing film has the same structure as the above-mentioned side of the polarizing film of Examples 4 to 8 and Comparative Example 8. On the other hand, by the same method as in Example 3, the following polarizing film protective film is bonded to the other side of the polarizing film as a polarizing film protective film having the same structure as the above-mentioned other side of the polarizing film of Comparative Example 5, i.e., a polarizing film protective film having light absorption ability, by doping a curable adhesive so that the total thickness of the curable adhesive reaches 1.0 μm. The polarizing film protective film is formed by a triacetyl cellulose film containing a light absorber and a hard coating layer having no light absorption ability disposed on the visible side thereof. In addition, the water content of the polarizing film laminate is changed.
[0320] The other conditions are the same as those in Example 7.
[0321] [Example 9]
[0322] When the polarizing film of Example 4 was produced, the concentration of the iodine aqueous solution and the immersion time were adjusted during the dyeing process to change the iodine concentration.
[0323] The rest is the same as in the fourth embodiment.
[0324] [Example 10]
[0325] When the polarizing film of Example 3 was produced, the concentration of the iodine aqueous solution and the immersion time were adjusted during the dyeing process to change the iodine concentration.
[0326] In addition, when preparing the polarizing film laminate of Example 3, a transparent protective film having a modified acrylic polymer having a lactone ring structure bonded to one side of the polarizing film was used instead of a transparent protective film having a thickness of 20 μm. In addition, the water content of the polarizing film laminate was changed.
[0327] The rest is the same as in the third embodiment.
[0328] [Comparative Example 10]
[0329] When the polarizing film of Example 9 was produced, the concentration of the iodine aqueous solution and the immersion time were adjusted during the dyeing process to change the iodine concentration.
[0330] When preparing the polarizing film laminate of Example 9, a transparent protective film (manufactured by Nitto Denko Corporation) with a thickness of 30 μm formed of a modified acrylic polymer having a lactone ring structure was bonded to one side of the polarizing film via a doped curable adhesive in the same manner as in Example 3. On the other hand, the following polarizing film protective film was bonded to the other side of the polarizing film as a polarizing film protective film with light absorption ability via a doped curable adhesive in the same manner as in Example 3 so that the total thickness of the curable adhesive reached 1.0 μm. The polarizing film protective film was formed with a hard coating layer (manufactured by Nitto Denko Corporation, thickness 9 μm) without light absorption ability on a triacetyl cellulose film (manufactured by Fujifilm Corporation, trade name "TJ40ULF", thickness 40 μm) containing a light absorber. In addition, the moisture content of the polarizing film laminate was changed.
[0331] The rest is the same as in the ninth embodiment.
[0332] [Example 11]
[0333] When the polarizing film of Example 3 was produced, the concentration of the iodine aqueous solution and the immersion time were adjusted during the dyeing process to change the iodine concentration.
[0334] In addition, when preparing the polarizing film laminate of Example 3, a doping curing adhesive was used as an adhesive, more specifically, an aqueous solution containing a polyvinyl alcohol resin having an acetoacetyl group (average degree of polymerization 1200, saponification degree 98.5 mol%, acetoacetylation degree 5 mol%) and hydroxymethyl melamine in a weight ratio of 3:1. Using this adhesive, a transparent protective film with a thickness of 25 μm formed by cellulose triacetate was bonded to one side of the polarizing film. Specifically, the doping curing adhesive was applied in a manner so that the total thickness reached 1.0 μm, and bonding was performed using a roller machine. On the other hand, on the other side of the polarizing film, the polarizing film protective film used in Example 1, that is, a polarizing film protective film formed by a cellulose triacetate film containing a light absorber and a hard coating layer containing a light absorber arranged on its visible side, was bonded using a doping curing adhesive instead of an ultraviolet curing adhesive as a polarizing film protective film having light absorption ability. Then, the film was dried by heating at 70° C. for 5 minutes in an oven to obtain a polarizing film laminate having a polarizing film, a polarizing film protective film having no light absorption capability arranged on one side of the polarizing film, and a polarizing film protective film having light absorption capability arranged on the other side.
[0335] [Comparative Example 11]
[0336] When preparing the polarizing film laminate of Example 11, a doping curing adhesive, more specifically, an aqueous solution containing a polyvinyl alcohol resin having an acetoacetyl group (average degree of polymerization 1200, saponification degree 98.5 mol%, acetoacetylation degree 5 mol%) and hydroxymethyl melamine in a weight ratio of 3:1, was used as an adhesive. Using this adhesive, a transparent protective film with a thickness of 25 μm formed of cellulose triacetate was bonded to one side of the polarizing film. Specifically, the doping curing adhesive was applied in such a manner that the total thickness reached 1.0 μm, and bonding was performed using a roller machine. On the other hand, the polarizing film protective film used in Comparative Example 5, i.e., a polarizing film protective film formed of a cellulose triacetate film containing a light absorber and a hard coating layer not containing a light absorber disposed on its visible side, was bonded to the other side of the polarizing film as a polarizing film protective film having light absorption capability using the same doping curing adhesive as one side instead of an ultraviolet curing adhesive.
[0337] [Comparative Example 12]
[0338] When the polarizing film of Example 11 was produced, the concentration of the iodine aqueous solution and the immersion time were adjusted during the dyeing process to change the iodine concentration.
[0339] The rest is the same as in Example 11.
[0340] [Comparative Example 13]
[0341] When the polarizing film of Comparative Example 11 was produced, the concentration of the iodine aqueous solution and the immersion time were adjusted during the dyeing process to change the iodine concentration.
[0342] The rest is the same as in Comparative Example 11.
[0343] 4-1. Reliability test
[0344] Using the polarizing film laminate 12 obtained in the embodiment and the comparative example, Figure 5 As shown, glass plates (slide glass manufactured by Matsunami Glass, product number: S2000423, specifications: water-edge-grinded 65×165 mm, thickness 1.3 mm) were laminated on both surfaces of a polarizing film laminate 12 via transparent adhesives 11 and 13, respectively, and this was used as a sample.
[0345] As the adhesive, CS98210US (manufactured by Nitto Denko Corporation) with a thickness of 200 μm was used on one side of the polarizing film laminate, and an acrylic adhesive (thickness of 20 μm) used for a polarizing film laminate (manufactured by Nitto Denko Corporation) of CRT1794YCU was used on the other side of the polarizing film laminate. The acrylic adhesive for the other side was obtained as follows: 99 parts by weight of butyl acrylate (the same below), 1.0 part of 4-hydroxybutyl acrylate, and 0.3 part of 2,2'-azobisisobutyronitrile were added together with ethyl acetate to a reaction container equipped with a condenser, a nitrogen inlet pipe, a thermometer, and a stirring device, and reacted at 60° for 4 hours under a nitrogen stream. Ethyl acetate was then added to the reaction solution to obtain a solution containing an acrylic polymer having a weight average molecular weight of 1.65 million (solid content concentration 30% by weight), and 0.3 parts of dibenzoyl peroxide (NOF Corporation: NYPER BMT), 0.1 parts of trimethylolpropane xylene diisocyanate (Mitsui Takeda Chemicals, Inc.: Takenate D110N), and 0.2 parts of a silane coupling agent (A-100, acetoacetyl-containing silane coupling agent, manufactured by Midoriken Chemical Co., Ltd.) were added per 100 parts of the solid content of the acrylic polymer solution.
[0346] A xenon light irradiation test was performed on each sample using a xenon weather tester (NX75 manufactured by Suga Test Instruments Co., Ltd.).
[0347] (Xenon light irradiation test)
[0348] In an atmosphere with a black panel temperature of 89°C and 30% RH, the accumulated irradiance is 100 W / m in the wavelength range of 300 to 400 nm. 2 The sample was irradiated with xenon light for 200 hours. The light source used was a xenon lamp (manufactured by Suga Test Instruments Co., Ltd.) equipped with a daylight filter (manufactured by Suga Test Instruments Co., Ltd.). After irradiation for 200 hours, decolorization and reddening by heating were evaluated, and polyeneization was also evaluated after irradiation for 200 hours.
[0349] 4-2. Evaluation criteria
[0350] The evaluation criteria for polyene formation, red change upon heating, and discoloration are shown below.
[0351] <Polyene>
[0352] The single-body transmittance of the sample was measured before and after the xenon light irradiation test, and the change in the single-body transmittance ΔTs was calculated by the following formula.
[0353] (Formula) ΔTs = Ts xenon 200 - Ts 0
[0354] Among them, Ts 0 TsXenon200 is the single transmittance of the sample before xenon irradiation, and TsXenon200 is the single transmittance after the xenon light irradiation test.
[0355] When the monomer transmittance after 200 hours of xenon light irradiation is -0.5 or more compared to the monomer transmittance before irradiation, it is evaluated that the problem of polyene is within the allowable range and there is no problem. When the monomer transmittance after 200 hours of xenon light irradiation is -0.2 or more compared to the monomer transmittance before irradiation, it is evaluated that there is no problem with polyene. In addition, when the monomer transmittance after 200 hours of xenon light irradiation is the same as the monomer transmittance before irradiation, or is greater than the monomer transmittance before irradiation, it is evaluated that there is no problem with polyene.
[0356] The single-piece transmittance of the sample was measured using a spectrophotometer (product name "DOT-3" manufactured by Murakami Color Research Laboratory Co., Ltd.) The single-piece transmittance can be determined based on JIS Z8701.
[0357] <Discoloration / Heating Reddening>
[0358] Before and after the xenon light irradiation test, the samples were arranged in an orthogonal Nicol manner, and the orthogonal transmittance (%) at a wavelength of 410 nm and a wavelength of 700 nm was measured by the above-mentioned spectrophotometer, and the change ΔHs was calculated. 410 and ΔHs 700 .
[0359] The case where both of the following two conditions were satisfied was evaluated as "discoloration" of the sample.
[0360] ·Change ΔHs 410 More than 1%
[0361] ·Change ΔHs 700 More than 5%
[0362] In other words, after 200 hours of xenon light irradiation, when the change in the cross transmittance at a wavelength of 410 nm was less than 1% and the change in the cross transmittance at a wavelength of 700 nm was less than 5%, it was evaluated that there was no problem of discoloration.
[0363] In addition, the case where the following conditions were satisfied was evaluated as the "heating reddening" of the sample.
[0364] ·Change ΔHs 410 Less than 1%
[0365] ·Change ΔHs700 More than 5%
[0366] In other words, after 200 hours of xenon light irradiation, when the change in cross transmittance at a wavelength of 410 nm was 1% or more and the change in cross transmittance at a wavelength of 700 nm was less than 5%, it was evaluated that there was no problem of heat reddening.
[0367] The evaluation results in each of the Examples and Comparative Examples are shown in Tables 2 and 3 below.
[0368]
[0369]
[0370] 5. Summary of evaluation results
[0371] Figure 6 The results of the embodiment and the comparative example are plotted in an xy orthogonal coordinate system with the embodiment as the center. In addition, when the results of the embodiment and the comparative example overlap, the results of the "embodiment" are shown. On the contrary, Figure 7 The results of the examples and comparative examples are plotted similarly with the comparative example as the center. In addition, when the results of the examples and comparative examples overlap, the results of the "comparative example" are shown. The x-axis (horizontal axis) represents the iodine concentration (wt.%) of the polarizing film, and the y-axis (vertical axis) represents the moisture content (g / m 2 ).
[0372] (1) According to the results of the mapping and technical common sense, it can be roughly considered that when the iodine concentration is small and the water content is too small, the problem of heating red discoloration under high temperature conditions is likely to occur. On the other hand, when the iodine concentration is large and the water content is too large, the problems of polyene and decolorization are likely to occur. In addition, it can be considered that when the iodine concentration is small and the water content is too large, the problem of decolorization under high temperature and high humidity conditions is likely to occur. In this case, as the iodine concentration increases, the problem of polyene is likely to occur. In particular, between decolorization and polyene, a transition region between them is also observed (Comparative Example 1). It should be noted that although in Figure 6 The result of heating red change is not specifically shown in the literature, but it is clear from common technical knowledge that this phenomenon will occur when the iodine concentration is too low and the water content is too low.
[0373] On the other hand, when the iodine concentration and the water content are neither too large nor too small and are in a state of balance, the iodine concentration and the water content fall within a given region that can be in such a balance, and all the problems of red discoloration by heating, polyeneization and decolorization can be solved comprehensively. For example, the results of the examples are all located on the upper side of the dividing line "α", i.e., y = (239.4-35x) / 42, and on the lower side of the dividing line "β", i.e., y = (344.4-44x) / 52, and the dividing line "α" is the periphery of the plot of the results of Example 2, which shows a small water content but a large iodine concentration, i.e., an iodine concentration of 6.0 wt.% and a water content of 0.7 g / m 2 The coordinate point (hereinafter referred to as the first coordinate point) and the surrounding area of the plot showing the results of Example 7 with the lowest iodine concentration but the largest water content, that is, the iodine concentration is 1.8wt.% and the water content is 4.2g / m 2 The dividing line "β" is a line of the coordinate point of the second coordinate point (hereinafter referred to as the second coordinate point), and the dividing line "β" is the periphery of the plotted result of Example 6 which shows the largest water content but the smallest iodine concentration, that is, the iodine concentration is 1.8wt.% and the water content is 5.1g / m 2 The coordinate point (hereinafter referred to as the third coordinate point) and the surrounding area of the plotted result of Example 1 showing the (maximum) iodine concentration and the (minimum) moisture content, i.e., the iodine concentration is 7.0 wt.% and the moisture content is 0.7 g / m 2 The line of the coordinate point (hereinafter referred to as the fifth coordinate point) of the reference point can be obtained. Thus, at least the area separated by these separation lines "α" and "β" can be obtained as a line representing the conditions necessary for comprehensively solving all the problems of reddening, polyeneization and decolorization. In addition, if the results of the comparative example are also considered, the coordinate points that do not include the comparative example but connect the third coordinate point and the fifth coordinate point, namely, iodine concentration 5.7wt.% and moisture content 2.6g / m 2 The coordinate point (hereinafter referred to as the fourth coordinate point). That is, the results of the embodiment are all located on the lower side of the dividing line "γ1" passing through the third coordinate point and the fourth coordinate point, that is, y = (243.9-25x) / 39, and the dividing line "γ2" passing through the fourth coordinate point and the fifth coordinate point, that is, y = (142.1-19x) / 13. It should be noted that these dividing lines "α", "β", "γ1", and "γ2" have nothing to do with the film thickness of the polarizing film. Specifically, they are applicable to all polarizing films with a film thickness of about 4 to 30 μm.
[0374] (2) It can be seen from this that, in particular, with respect to all polarizing films having a film thickness of about 4 to 30 μm, when the iodine concentration and the water content of the polarizing film laminate are contained in the following region, all problems of "polyeneization", "bleaching" and "heat reddening" can be solved comprehensively. The region is, for example, the region surrounded by a to e, and more specifically, the region surrounded by the iodine concentration of 6.0 wt.% and the water content of 0.7 g / m 2 The first coordinate point ("a" in the figure) and the iodine concentration are 1.8wt.% and the moisture content is 4.2g / m 2 The first line segment of the second coordinate point ("b" in the figure) connects the second coordinate point "b" and the iodine concentration of 1.8wt.% and the moisture content of 5.1g / m 2 The second line segment of the third coordinate point ("c" in the figure), connecting the third coordinate point "c" and the iodine concentration of 5.7wt.% and the water content of 2.6g / m 2 The third line segment of the fourth coordinate point ("d" in the figure), connecting the fourth coordinate point "d" and the iodine concentration of 7.0wt.% and the water content of 0.7g / m 2 The area surrounded by the fourth line segment connecting the fifth coordinate point ("e" in the figure) and the fifth line segment connecting the first coordinate point "a" and the fifth coordinate point "e".
[0375] (3) Similarly, it can be seen that, in particular, with respect to a polarizing film having a film thickness of about 11 to 30 μm, when the iodine concentration and the water content of the polarizing film laminate are contained in the following region, all problems of "polyeneization", "bleaching" and "heat reddening" can be solved comprehensively. The region is the region surrounded by f, b, c, and g, and more specifically, the region surrounded by the iodine concentration of 4.5 wt.% and the water content of 1.9 g / m 2 The sixth line segment connecting the sixth coordinate point ("f" in the figure) and the second coordinate point "b", the second line segment connecting the second coordinate point "b" and the third coordinate point "c", the second line segment connecting the third coordinate point "c" and the iodine concentration of 4.5wt.% and the moisture content of 3.4g / m 2 The area surrounded by the seventh line segment connecting the seventh coordinate point ("g" in the figure) and the eighth line segment connecting the sixth coordinate point "f" and the seventh coordinate point "g".
[0376] It is believed that the iodine concentration is 4.0 wt.% and the water content is 2.4 g / m3 at the sixth coordinate point "f". 2 The eighth coordinate point ("f-1" in the figure), the seventh coordinate point "g" has an iodine concentration of 4.0wt.% and a water content of 3.7g / m 2 In the case of the ninth coordinate point ("g-1" in the figure), a preferred result can be obtained. In addition, it is considered that at the sixth coordinate point "f" the iodine concentration is 3.7wt.% and the water content is 2.6g / m 2When the tenth coordinate point ("h" in the figure) and the seventh coordinate point "g" are the fourth coordinate point "d", a preferred result can also be obtained.
[0377] (4) In addition, especially with respect to a polarizing film having a film thickness of about 4 to 11 μm, when the iodine concentration and the moisture content of the polarizing film stack are contained in the following area, all problems of "polyeneization", "bleaching" and "heat reddening" can be solved comprehensively. The area is an area surrounded by a, h, d, and e. More specifically, it is an area surrounded by the ninth line segment connecting the first coordinate point "a" and the tenth coordinate point "h", the eleventh line segment connecting the tenth coordinate point "h" and the fourth coordinate point "d", and the fifth line segment connecting the first coordinate point "a" and the fifth coordinate point "e".
[0378] In addition, according to Figure 6 and Figure 7 It is clear from the comparison of the above that polyeneization can be prevented particularly effectively by providing a light absorbing layer having light absorbing ability.
[0379] It should be noted that the above embodiment shows an example in which a light absorber is added to the polarizing film protective film. However, by making the transparent adhesive (OCA) 13 (transparent adhesive layer) contain a light absorber (ultraviolet absorber), the same result can be obtained when the above reliability test is performed. In addition, the cover plate 14 (transparent cover plate) contains a light absorber (ultraviolet absorber), and the same result can be obtained when the above reliability test is performed. It should be noted that in this case, the reliability test is performed using the cover plate 14 instead of a glass plate (slide glass manufactured by Matsunami Glass, product number: S2000423, specifications: water-edge polished 65×165mm, thickness 1.3mm) closer to the visible side than the transparent adhesive 13.
Claims
1. A polarizing film laminate, comprising: A polarizing film formed of a polyvinyl alcohol resin, and an optically transparent polarizing film protective film bonded to at least the visible side of the polarizing film directly or via another optical film, in, The iodine concentration wt.% of the polarizing film is taken as the x-axis, and the moisture content g / m 2 In an xy orthogonal coordinate system with the y-axis as the axis, the polarizing film laminate has an iodine concentration and a water content contained in the following area, which is surrounded by a first line segment connecting the first coordinate point and the second coordinate point, a second line segment connecting the second coordinate point and the third coordinate point, a third line segment connecting the third coordinate point and the fourth coordinate point, a fourth line segment connecting the fourth coordinate point and the fifth coordinate point, and a fifth line segment connecting the first coordinate point and the fifth coordinate point, The first coordinate point is an iodine concentration of 6.0 wt.% and a water content of 0.7 g / m 2 The coordinate point of The second coordinate point is an iodine concentration of 1.8 wt.% and a water content of 4.2 g / m 2 The coordinate point of The third coordinate point is an iodine concentration of 1.8 wt.% and a moisture content of 5.1 g / m 2 The coordinate point of The fourth coordinate point is iodine concentration 5.7wt.% and water content 2.6g / m 2 The coordinate point of The fifth coordinate point is an iodine concentration of 7.0 wt.% and a water content of 0.7 g / m 2 The coordinate point of The polarizing film protective film is a light absorbing layer having light absorbing ability, and has a transmittance of 5% or less to light at a wavelength of 380 nm.
2. The polarizing film laminate according to claim 1, in, The polarizing film has a thickness of 4 to 30 μm.
3. A polarizing film laminate, comprising: A polarizing film formed of a polyvinyl alcohol resin, and an optically transparent polarizing film protective film bonded to at least the visible side of the polarizing film directly or via another optical film, in, The iodine concentration wt.% of the polarizing film is taken as the x-axis, and the moisture content g / m 2 In an xy orthogonal coordinate system with the y-axis as the axis, the polarizing film laminate has an iodine concentration and a water content contained in the following area, which is surrounded by a sixth line segment connecting the sixth coordinate point and the second coordinate point, a second line segment connecting the second coordinate point and the third coordinate point, a seventh line segment connecting the third coordinate point and the seventh coordinate point, and an eighth line segment connecting the sixth coordinate point and the seventh coordinate point, The sixth coordinate point is an iodine concentration of 4.5 wt.% and a water content of 1.9 g / m 2 The coordinate point of The second coordinate point is an iodine concentration of 1.8 wt.% and a water content of 4.2 g / m 2 The coordinate point of The third coordinate point is an iodine concentration of 1.8 wt.% and a moisture content of 5.1 g / m 2 The coordinate point of The seventh coordinate point is iodine concentration 4.5wt.% and water content 3.4g / m 2 The coordinate point of The polarizing film protective film is a light absorbing layer having light absorbing ability, and the transmittance of light at a wavelength of 380 nm is 5% or less.
4. The polarizing film laminate according to claim 3, in, The sixth coordinate point has an iodine concentration of 4.0 wt.% and a water content of 2.4 g / m 2 The eighth coordinate point, the seventh coordinate point is iodine concentration 4.0wt.% and water content 3.7g / m 2 The ninth coordinate point.
5. The polarizing film laminate according to claim 3, in, The sixth coordinate point has an iodine concentration of 3.7 wt.% and a water content of 2.6 g / m 2 The seventh coordinate point is iodine concentration 5.7wt.% and water content 2.6g / m 2 The fourth coordinate point of .
6. The polarizing film laminate according to claim 3 or 4, in, The polarizing film has a thickness of 11 to 30 μm.
7. A polarizing film laminate, comprising: A polarizing film formed of a polyvinyl alcohol resin, and an optically transparent polarizing film protective film bonded to at least the visible side of the polarizing film directly or via another optical film, in, The iodine concentration wt.% of the polarizing film is taken as the x-axis, and the moisture content g / m 2 In an xy orthogonal coordinate system with the y-axis as the axis, the polarizing film stack has an iodine concentration and a water content contained in the following area, which is surrounded by a ninth line segment connecting the first coordinate point and the tenth coordinate point, a tenth line segment connecting the tenth coordinate point and the fourth coordinate point, an eleventh line segment connecting the fourth coordinate point and the fifth coordinate point, and a fifth line segment connecting the first coordinate point and the fifth coordinate point, The first coordinate point is an iodine concentration of 6.0 wt.% and a water content of 0.7 g / m 2 The coordinate point of The tenth coordinate point has an iodine concentration of 3.7 wt.% and a water content of 2.6 g / m 2 The coordinate point of The fourth coordinate point is iodine concentration 5.7wt.% and water content 2.6g / m 2 The coordinate point of The fifth coordinate point is an iodine concentration of 7.0 wt.% and a water content of 0.7 g / m 2 The coordinate point of The polarizing film protective film is a light absorbing layer having light absorbing ability, and has a transmittance of 5% or less to light at a wavelength of 380 nm.
8. The polarizing film laminate according to claim 7, in, The polarizing film has a thickness of 4 to 11 μm.
9. The polarizing film laminate according to any one of claims 1 to 8, in, The polarizing film protective film has a transmittance of light of 35% or less at a wavelength of 390 nm.
10. The polarizing film laminate according to any one of claims 1 to 9, in, The polarizing film protective film has a transmittance of light at a wavelength of 400 nm of 70% or less.
11. The polarizing film laminate according to any one of claims 1 to 10, in, The polarizing film contains zinc.
12. The polarizing film laminate according to any one of claims 1 to 11, in, For a sample consisting of the polarizing film laminate and glass plates laminated on both sides of the polarizing film laminate via an adhesive, a black panel temperature of 89°C was set in an atmosphere of 30% RH in a wavelength range of 300 to 400 nm with an integrated radiant illuminance of 100 W / m 2 After 200 hours of xenon light irradiation, the single body transmittance was -0.5 or more compared with the single body transmittance before irradiation.
13. The polarizing film laminate according to any one of claims 1 to 12, in, For a sample consisting of the polarizing film laminate and glass plates laminated on both sides of the polarizing film laminate via an adhesive, a black panel temperature of 89°C was set in an atmosphere of 30% RH in a wavelength range of 300 to 400 nm with an integrated radiant illuminance of 100 W / m 2 After irradiation with xenon light for 200 hours, the change in the cross transmittance at a wavelength of 410 nm was less than 1%, and the change in the cross transmittance at a wavelength of 700 nm was less than 5%.
14. The polarizing film laminate according to any one of claims 1 to 13, in, For a sample consisting of the polarizing film laminate and glass plates laminated on both sides of the polarizing film laminate via an adhesive, a black panel temperature of 89°C was set in an atmosphere of 30% RH in a wavelength range of 300 to 400 nm with an integrated radiant illuminance of 100 W / m 2 After irradiation with xenon light for 200 hours, the amount of change in the orthogonal transmittance at a wavelength of 410 nm was 1% or more, and the amount of change in the orthogonal transmittance at a wavelength of 700 nm was less than 5%.
15. An optical display panel comprising: Optical display unit; The polarizing film laminate according to any one of claims 1 to 14, which is bonded to one surface of the optical display unit directly or via another optical film; and an optically transparent cover plate disposed along the polarizing film stack on a side of the polarizing film stack opposite to the optical display unit, The optical display unit, the polarizing film stack, and the transparent cover are bonded together by a transparent adhesive layer filled therebetween without any gaps.
16. The optical display panel according to claim 15, in, The transparent cover has a function of a capacitive touch sensor.
17. The optical display panel according to claim 16, in, An ITO layer serving as a component of a capacitive touch sensor is provided between the transparent cover plate and the polarizing film laminate.
18. A polarizing film laminate with a transparent adhesive layer, comprising: A polarizing film laminate comprising a polarizing film formed of a polyvinyl alcohol-based resin and an optically transparent polarizing film protective film bonded to at least a visible side surface of the polarizing film directly or via another optical film; and A transparent adhesive layer laminated on the viewing side of the polarizing film laminate, in, The iodine concentration wt.% of the polarizing film is taken as the x-axis, and the moisture content g / m 2 In an xy orthogonal coordinate system with the y-axis as the xy axis, the polarizing film laminate with the transparent adhesive layer has an iodine concentration and a water content contained in the following area, which is surrounded by a first line segment connecting a first coordinate point and a second coordinate point, a second line segment connecting the second coordinate point and a third coordinate point, a third line segment connecting the third coordinate point and a fourth coordinate point, a fourth line segment connecting the fourth coordinate point and a fifth coordinate point, and a fifth line segment connecting the first coordinate point and the fifth coordinate point, The first coordinate point is an iodine concentration of 6.0 wt.% and a water content of 0.7 g / m 2 The coordinate point of The second coordinate point is an iodine concentration of 1.8 wt.% and a water content of 4.2 g / m 2 The coordinate point of The third coordinate point is an iodine concentration of 1.8 wt.% and a moisture content of 5.1 g / m 2 The coordinate point of The fourth coordinate point is iodine concentration 5.7wt.% and water content 2.6g / m 2 The coordinate point of The fifth coordinate point is an iodine concentration of 7.0 wt.% and a water content of 0.7 g / m 2 The coordinate point of In the transparent adhesive layer and the polarizing film protective film, at least the transparent adhesive layer is a light absorbing layer having light absorbing ability. The laminate of the transparent adhesive layer and the polarizing film protective film has a transmittance of 5% or less with respect to light at a wavelength of 380 nm.
19. A polarizing film laminate with a transparent adhesive layer, comprising: A polarizing film laminate comprising a polarizing film formed of a polyvinyl alcohol-based resin and an optically transparent polarizing film protective film bonded to a surface of the polarizing film opposite to a visible side directly or via another optical film; and A transparent adhesive layer laminated on the viewing side of the polarizing film laminate, in, The iodine concentration wt.% of the polarizing film is taken as the x-axis, and the moisture content g / m 2 In an xy orthogonal coordinate system with the y-axis as the xy axis, the polarizing film laminate with the transparent adhesive layer has an iodine concentration and a water content contained in the following area, which is surrounded by a first line segment connecting a first coordinate point and a second coordinate point, a second line segment connecting the second coordinate point and a third coordinate point, a third line segment connecting the third coordinate point and a fourth coordinate point, a fourth line segment connecting the fourth coordinate point and a fifth coordinate point, and a fifth line segment connecting the first coordinate point and the fifth coordinate point, The first coordinate point is an iodine concentration of 6.0 wt.% and a water content of 0.7 g / m 2 The coordinate point of The second coordinate point is an iodine concentration of 1.8 wt.% and a water content of 4.2 g / m 2 The coordinate point of The third coordinate point is an iodine concentration of 1.8 wt.% and a moisture content of 5.1 g / m 2 The coordinate point of The fourth coordinate point is iodine concentration 5.7wt.% and water content 2.6g / m 2 The coordinate point of The fifth coordinate point is an iodine concentration of 7.0 wt.% and a water content of 0.7 g / m 2 The coordinate point of The transparent adhesive layer is a light absorbing layer having light absorbing ability. The transparent adhesive layer has a transmittance of 5% or less with respect to light at a wavelength of 380 nm.
20. A polarizing film assembly comprising: A polarizing film laminate comprising a polarizing film formed of a polyvinyl alcohol-based resin and an optically transparent polarizing film protective film bonded to at least a visible side of the polarizing film directly or via another optical film; a transparent adhesive layer laminated on the viewing side of the polarizing film laminate; and An optically transparent cover plate is laminated on the visible side of the transparent adhesive layer. in, The iodine concentration wt.% of the polarizing film is taken as the x-axis, and the moisture content g / m 2 In an xy orthogonal coordinate system with the y-axis as the axis, the polarizing film assembly has an iodine concentration and a water content contained in an area surrounded by a first line segment connecting a first coordinate point and a second coordinate point, a second line segment connecting the second coordinate point and a third coordinate point, a third line segment connecting the third coordinate point and a fourth coordinate point, a fourth line segment connecting the fourth coordinate point and a fifth coordinate point, and a fifth line segment connecting the first coordinate point and the fifth coordinate point, The first coordinate point is an iodine concentration of 6.0 wt.% and a water content of 0.7 g / m 2 The coordinate point of The second coordinate point is an iodine concentration of 1.8 wt.% and a water content of 4.2 g / m 2 The coordinate point of The third coordinate point is an iodine concentration of 1.8 wt.% and a moisture content of 5.1 g / m 2 The coordinate point of The fourth coordinate point is iodine concentration 5.7wt.% and water content 2.6g / m 2 The coordinate point of The fifth coordinate point is an iodine concentration of 7.0 wt.% and a water content of 0.7 g / m 2 The coordinate point of Among the polarizing film protective film, the transparent adhesive layer and the transparent cover plate, at least the transparent cover plate is a light absorbing layer having light absorbing capability. The laminate of the polarizing film protection film, the transparent adhesive layer, and the transparent cover plate has a transmittance of 5% or less with respect to light at a wavelength of 380 nm.
21. A polarizing film assembly comprising: A polarizing film laminate comprising a polarizing film formed of a polyvinyl alcohol-based resin and an optically transparent polarizing film protective film bonded to the surface of the polarizing film opposite to the visible side directly or via another optical film; a transparent adhesive layer laminated on the viewing side of the polarizing film laminate; and An optically transparent cover plate is laminated on the visible side of the transparent adhesive layer. in, The iodine concentration wt.% of the polarizing film is taken as the x-axis, and the moisture content g / m 2 In an xy orthogonal coordinate system with the y-axis as the axis, the polarizing film assembly has an iodine concentration and a water content contained in an area surrounded by a first line segment connecting a first coordinate point and a second coordinate point, a second line segment connecting the second coordinate point and a third coordinate point, a third line segment connecting the third coordinate point and a fourth coordinate point, a fourth line segment connecting the fourth coordinate point and a fifth coordinate point, and a fifth line segment connecting the first coordinate point and the fifth coordinate point, The first coordinate point is an iodine concentration of 6.0 wt.% and a water content of 0.7 g / m 2 The coordinate point of The second coordinate point is an iodine concentration of 1.8 wt.% and a water content of 4.2 g / m 2 The coordinate point of The third coordinate point is an iodine concentration of 1.8 wt.% and a moisture content of 5.1 g / m 2 The coordinate point of The fourth coordinate point is iodine concentration 5.7wt.% and water content 2.6g / m 2 The coordinate point of The fifth coordinate point is an iodine concentration of 7.0 wt.% and a water content of 0.7 g / m 2 The coordinate point of Among the transparent adhesive layer and the transparent cover plate, at least the transparent cover plate is a light absorbing layer having light absorbing capability. The laminate of the transparent adhesive layer and the transparent cover plate has a transmittance of 5% or less with respect to light at a wavelength of 380 nm.
Citation Information
Patent Citations
Polarizer, polarizing plate and liquid crystal display device
JP2003029042A
Polarizing plate protection film, and polarizing plate and liquid crystal display using same
JP2006184883A
Polarizing plate and image display device, and manufacturing method of those
JP2014102353A
Pressure-sensitive adhesive layer-bearing polarizing film for transparent conductive coating, laminate, and image display device
CN104422979A
Active-energy-ray-curable adhesive composition, laminated polarizing film, method for producing same, laminated optical film, and image display device
CN109072013A
